Digital model reconstruction of shield tunnels based on 3D point cloud - Yu Li; Huai-Na Wu; Dong-Lin Feng; Si-Qi Yang; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Long-term mineral fertilization increases microbial carbon use efficiency and necromass in upland but not in paddy soils - Ziyi Li; Di Lin; Huimin Zhang; Chengjie Ren; Yu'’e Li; Andong Cai (CATENA, 2026)

Combined targeting poly (ADP-ribose) polymerase and receptor tyrosine kinase inhibits ovarian clear cell carcinoma progression through disrupted ribosome biogenesis - Chiao-Yun Lin; An-Shine Chao; Angel Chao; Ren-Chin Wu; Alice L. Yu; Chiung-Hui Fu; Yu-Chuan Teng; Ruby Yun-Ju Huang; Chyong-Huey Lai (Journal of Molecular Medicine, 2026)

Two-stage instance segmentation method based on Tunnel-SPVNet for shield tunnel segments - Yu Li; Huai-Na Wu; Dong-Lin Feng; Yu-Liang Li; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

Accumulation, elimination and biotransformation of paralytic shellfish toxins in ark shell Anadara kagoshimensis - Zhuo-Ru Lin; Hui-Xia Geng; Sara A. Cunha; Chang Xu; Ren-Cheng Yu (Marine Pollution Bulletin, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Nanoengineered Ce2CaMoO6 double perovskites derived oxide decorated on 2D P@g-C3N4 nanohybrid for the sensitive electrochemical sensing of antiscald agent diphenylamine in food and environmental matrices - Evangeline Jafneel Nixon; Abishek Jayapaul; Sanjay Ballur Prasanna; Chuan-Ming Tseng; Yu-Chien Lin; Da-Hua Wei; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2026)

Single-cell multi-omics dissects transcript isoform and immune repertoire dynamics in human immunosenescence - Yuhui Zheng; Ze-Hui Ren; Yafei Yang; Wenteng Liu; Fupeng Li; Yajun Zuo; Tao Zeng; Xue Wang; Xiumei Lin; Xinyue Zhu; Baibing Guan; Wenwen Zhou; et al. (Science China Life Sciences, 2026)

Investigation on performance-based deformation control criteria for shield tunnel linings under typical adjacent construction disturbances - Dong-Lin Feng; Yu Li; Huai-Na Wu; Si-Qi Yang; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Development of a Recombinant Goose Parvovirus VP2 Neutralizing Epitope-Containing Region Vaccine Adjuvanted with IL-2 and FliC for Enhanced Immune Responses and Protection Against Challenge - Qing Wu; Xinyu Li; Jiaxin Li; Ziran Liu; Lin Bai; Lin Zhang; Shujing Xia; Di Wu; Yuhan Jin; Xinyuan Shen; Yu Gao; Jingming Wang; et al. (The Veterinary Journal, 2026)

Neurotoxicological Concerns: Azole Fungicides as Mixed/Noncompetitive Inhibitors of Human and Rat 5α-Reductase 1 - Jiachen Lin; Yinghao Huang; Yilin Xu; Zhiqiang Yu; Chentao Ding; Mengru Li; Yingfen Ying; Ren-shan Ge; Yiluan Wang (Journal of Hazardous Materials, 2026)

Disruption of OsGONST3 reduces grain cadmium accumulation without yield penalty in field-grown rice - Jing Huang; Qiang Zhang; Fang Wei Yu; Ming Qing Liu; Huai Kang Jing; Shen Yun Wang; Hao Yu Wang; Jia Qi Li; Lu Zheng; Hua Shao; Xiao Lin He; Ren Fang Shen; et al. (Journal of Hazardous Materials, 2026)

True triaxial mechanical behavior and damage mechanisms of water-saturated shale under blasting dynamic disturbance - Chongyang Wang; Sijiang Wei; Dongming Zhang; Fake Ren; Yisha Pan; Yun Lin; Yu Wang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Toxin partitioning and sxtA4 expression in Alexandrium catenella under excess nitrogen supply - Ziru Lian; Chang Xu; Lin Guo; Jingxuan Li; Hao Huang; Ren-Cheng Yu (Harmful Algae, 2026)

Coupled effect of crack inclination and microstructure on the mechanical behavior of soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji; Tao Wang; Hao Wang; Hai Wang; Jun-Feng Ren (Engineering Geology, 2026)

Genomic mining of the terpene synthase family in magnoliids reveals novel clades - Fang Wang; Qiongqiong Lin; Zijian Zhang; Yunyang Yu; Mengxue Feng; Meixiu Lin; Yongjuan Ren; Liuming Luo; Xin Liu; Huan Liu; Sunil Kumar Sahu; Tong Wei; et al. (The Nucleus, 2026)

Mapping Whole-Brain Nonlinear Structure-Function Dynamics in Aging via Neural Granger Causality - Meng Niu; Shanli Ren; Chen Lin; QingChen Wang; Yongzhi Yin; Hanning Guo; Yu Fu (Brain Topography, 2026)

The cortical morphology of cingulate cortex and microarchitecture of cingulum bundle correlate with cancer pain and anxiety in lung cancer patients - Lin Tang; Xiaosong Lan; Xiaoyu Zhou; Yu Tang; Jiahui Zheng; Junhao Huang; Yong Tan; Jing Zhang; Hong Yu; Meng Lin; Hua Lan; Xinying Ren; et al. (Brain Imaging and Behavior, 2026)

Data-driven surrogate modeling of underwater vehicle wake and feature inversion of navigation parameters - Jie-Lin Ren; Wei-Pei Huang; Li Wang; Yu-Quan Wang; Kai-Qi Zhao; Peng-Nan Sun (Ocean Engineering, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Sedimentation rate changes revealing the evolution of circum–Arctic ice sheets since the Last Interglacial - Song Zhao; Dong Wu; Yu-Ying Zhang; Chao Cui; Sen Shan; Peng Ren; Lin-Sen Dong; Wei-Bin Zhang; Shu-Wei Sun; Yan-Guang Liu (Global and Planetary Change, 2026)

Highly uniform Cu/Fe-LDH synthesized by a UNISON method for MRI-guided ferroptosis/cuproptosis therapy and immune microenvironment remodeling of tumors - Chunmei Chen; Bin Ren; Qingdeng Fan; Ya Huang; Xinyu Chen; Yurun Huang; Hang Yi; Guochao Wu; Jing Yang; Lin Huang; Jiaoyang Zhu; Haolong Ma; et al. (Chemical Engineering Journal, 2026)

Bioinspired self-assembled gradient Janus bilayer aerogel enabling coupled solar desalination and purification of multicomponent oily emulsions - Peng Pi; Yu Feng; Wen Jung Li; Ling Pan; Youxi Lin; Linxi Hou; Zihao Huang; Qinwei Wang; Xuhui Wang; Zhiying Ren (Chemical Engineering Journal, 2026)

CYP4B1 inhibits lung adenocarcinoma metastasis by downregulating slug transcription via Sp1 - Sijia Wang; Yijie Liu; Yuan Yu; Shuwei Ren; Weiwei Lin; Kemeng Qiang; Haishan Huang; Honglei Jin (Clinical & Experimental Metastasis, 2026)

Spatiotemporal patterns of maritime incidents along the Northern Sea Route: A 20-year analysis - Yu Yan; Xi Wang; Zhikun Lin; Lei Ren; Qingkang Hou; Yingjun Xu (Ocean & Coastal Management, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Melatonin Modulates Antioxidant Properties, Carotenoid Accumulation, and Lignin Deposition to Enhance Adaptability to Salt Stress in Carrot - Guang-Long Wang; Yu-Jie Xu; Wang-Qi Jin; Lin-Yan Jia; Xu-Qin Ren; Ya-Nan Chen; Ai-Sheng Xiong (Journal of Plant Growth Regulation, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Synergistic transition binary metal oxide with multiwalled carbon nanotubes interfaces enabling sensitive electrochemical detection of preservative agent diphenylamine - Mosas Vinsy Arul Thomas; Sanjay Ballur Prasanna; Po-Chun Chen; Yu-Chien Lin; Rajalakshmi Sakthivel; Ting-Yu Liu; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2026)

Towards integrated pollution control in inland watersheds: addressing multiple challenges through watershed-scale technological systems and targeted control strategies - Mei-Yun Lu; Jie Ding; Xin-Lei Yu; Zi-Tong Zhao; Yi-Lin Zhao; Ji-Wei Pang; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Environmental Pollution, 2026)

Strategies for high-efficiency salt management in solar-driven interfacial evaporation - Jinjing Yang; Jing Zhang; Zhongxing Xu; Lin Ren; Longshi Rao; Junyang Tao; Yifeng Liao; Shudong Yu (Desalination, 2026)

Retraction notice to “hUC-MSCs lyophilized powder loaded polysaccharide ulvan driven functional hydrogel for chronic diabetic wound healing” [Carbohydrate Polymers 288 (2022) 119404] - Yu Ren; Aili Aierken; Li Zhao; Zhuangsheng Lin; Jingjing Jiang; Balun Li; Jinyi Wang; Jinlian Hua; Qin Tu (Carbohydrate Polymers, 2026)

In situ-based spectral characteristics of first-year landfast ice in eastern Liaodong Bay, Bohai sea - Qingkang Hou; Yu Yan; Zhikun Lin; Chenchen Yao; Jiayu Ding; Jinghan Xu; Chenyu Shu; Lei Ren; Yingjun Xu (International Journal of Remote Sensing, 2026)

In situ spectral analysis of sea ice contaminated with multiple substances in Liaodong Bay, Bohai Sea - Jinghan Xu; Yu Yan; Zhikun Lin; Qingkang Hou; Jiayu Ding; Chenchen Yao; Lei Ren; Chenyu Shu; Yingjun Xu (Marine Pollution Bulletin, 2026)

A stimulating effect induced by Bisphenol A bis (diphenylphosphate) in HepG2 cells via vascular endothelial growth factor (VEGF)/VEGF receptor axis - Jing An; Yuting Yi; Na Li; Miao Lin; Yufang Zhong; Guofa Ren; Yu Shang (Toxicology Letters, 2026)

Novel DUAL Z-SCHEME Bi2MoO6/SO3H@g-C3N4/ZnS photocatalyst enhanced by persulfate activation for rapid ofloxacin degradation: Integrated experimental and DFT studies - Imran Nasir Appau Zahir Hussain; Sanjay Ballur Prasanna; Po-Chun Chen; Yu-Chien Lin; Ching-Wei Tung; Ren-Jei Chung (Journal of Water Process Engineering, 2026)

Nature-inspired bicontinuous-topology 3D-printed TPMS solar interfacial evaporator - Yifeng Liao; Yizhe Liu; Lin Ren; Yujun Wei; Zhijian Huang; Jing Zhang; Zhongxin Xu; Jianing Wu; Junyang Tao; Shudong Yu; Shuo Wu (Chemical Engineering Journal, 2026)

Dual-Interface engineering and solvation structure regulation enable polyether based semi-solid polymer electrolyte in high voltage lithium metal battery - Yu-Jie Ren; Pei-Pei Chen; Kuan-Kuan Tian; Bai-Qin Xiong; Dong-Lin Zhao (Chemical Engineering Journal, 2026)

Discovery of anti-glioblastoma natural products based on andrographolide derivatives: efficiently identifying potential multi-target and multifunctional molecules through the integration of in silico methods and experimental verification - Ya-Lin Li; Jun Mao; Xin-Yu Zhou; Duan-Na Zhang; Yu-Zhi Li; Zhi-Xing Cao; Ji-Xia Ren (Molecular Diversity, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Reductant-driven structural evolution of zinc manganese oxide integrated beta-cyclodextrin for high-performance heavy metal detection - Monica Subramanian; Nandini Nataraj; I.-Hsuan Tung; Yu-Chien Lin; Cihun-Siyong Gong; Hsu-Wei Fang; Ren-Jei Chung (Process Safety and Environmental Protection, 2026)

Preserving the functional integrity of BiP1 is essential for rice storage protein export from the endoplasmic reticulum - Wenkun Yang; Tian Pan; Fan Wang; Yun Zhu; Kunneng Zhou; Binglei Zhang; Gexing Wan; Yu Chen; Yu Zhang; Xiejun Sun; Cailin Lei; Jie Wang; et al. (Plant Science, 2026)

Improved method for adjusting natural frequency of structures via stacked piezoelectric ceramic actuators - Wei Lin; Chaodong Xue; Yingjie Ren; Xuan Yao; Yu Zhang; Xiongliang Yao (Ocean Engineering, 2026)

Investigating intercity commuting using distance decay in a two-stage regression framework: A case study of Shenzhen Metropolitan Area in China - Zhaodong Zhang; Yaoyu Lin; Kezhou Ren; Li Guo; Yongxi Gong; Yu Liu (Journal of Transport Geography, 2026)

Strain-specific impacts of Pichia kudriavzevii on metabolite profiles and microbial community dynamics in Chinese Baijiu fermentation: Integrated metabolomics and metagenomics analysis - Boqin Zhang; Mengbo Wang; Jia Zheng; Chenxi Yu; Chunhui Wei; Junyu Ren; Shouying Sun; Guoming Wang; Jinhua Wang; Yanping Lu; Liangcai Lin; Cuiying Zhang (International Journal of Food Microbiology, 2026)

Parylene-C templated synthesis of hierarchical bismuth nanoflowers for reversible chloride-ion storage - Sanjay Ballur Prasanna; Jian-Lin Lyu; Yu-Lin Lee; Ren-Jei Chung; Hong-ming Ku; Po-Chun Chen (Chemical Engineering Journal, 2026)

Methotrexate-loaded FeAuGd nanoparticles for synergistic magnetic-hyperthermia and chemotherapy - Kayalvizhi Samuvel Muthiah; Lenin Subramanian; Yen-Lin Chen; Udesh Dhawan; Yu-Chien Lin; Ching-Li Tseng; Ren-Jei Chung (Chemical Engineering Journal, 2026)

Agroforestry balances plant–soil–microbe–enzyme interactions and improves its connectivity and homeostasis: Evidence from C:N:P stoichiometric networks - Qi-Wen Xu; Meng-Die Feng; Tian-Yang Li; Lin Xiong; Bo-Yu Ren; Yan-Zheng He; Bing-Hui He (Agriculture, Ecosystems & Environment, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Rambutan-inspired tri-layer architecture with regulated strain and lithium transport for high-capacity and stable lithium storage - Huan Du; Ganggang Ma; Ziqing Yin; Shaoqing Rao; Sheng Lin; Tianyi Zhang; Jingke Ren; Yucai Wu; Wei Zhang; Ruohan Yu; Dongyuan Zhao; Wei Li; et al. (Science Bulletin, 2026)

Redox-active flower-like ZnMoO4 decorated on 2D graphene oxide nanohybrid as an efficient catalyst for sensitive electrochemical detection of a nitrofuran derivative in environmental and biological matrices - Amulya Garadi; Sanjay Ballur Prasanna; Po-Chun Chen; Gagankumar Sakleshpur Kumar; Nandini Nataraj; Yu-Chien Lin; Xinke Liu; Ting-Yu Liu; Ren-Jei Chung (Journal of Water Process Engineering, 2026)

Coated ferrous sulfate requirement for alleviating hypoxia-induced hepatopancreatic inflammation in sub-adult grass carp (Ctenopharyngodon idella) - Yu-Juan Yang; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Hong-Yun Zhang; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Ying-Gu Kuang; Xiao-Qiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2026)

Dynamic cross-linked/conductive dual-network polyurethane for integrated EMI shielding, thermal management and motion sensing - Sijie Yu; Taotao Qiang; Xiaoyong Dong; Congcong Lin; Xiaonan Ruan; Guannan Dong; Haiyang Hu; Fangfang Dong; Chen Mi; Tianlin Chen; Chen Zhang; Longfang Ren (Chemical Engineering Journal, 2026)

Bioengineered functional scaffolds co-loaded with osteonectin and HA-internalizing osteoblasts for boosting bone regeneration - Wei Yang; Qin Zou; Chenxin Wang; Yuankun Ren; Rui Zhang; Mingyue Lin; Xueqi Zhang; Yu Liu; Boyang Wang; Wei Li; Li Jiang; Xiyu Li (Chemical Engineering Journal, 2026)

Environmental pyridinium disinfectants impair cortisol metabolism via 11β-hydroxysteroid dehydrogenase 2 inhibition: A cross-species risk evaluation - Chaochao Gong; Xiuzhi Zhang; Yu Zhang; Xishi Chen; Hao Lin; Ren-shan Ge; Youming Zhao (Chemico-Biological Interactions, 2026)

Gibberellic acid (GA) alleviates Al toxicity in rice (Oryza sativa) through a nitric oxide (NO) dependent pathway - Qi Jiang; Hao Yu Wang; Yong Qiang Gao; Ren Fang Shen; Yi Lin Xu; Qing Song Zheng; Xiao Fang Zhu (Planta, 2026)

Study on the discovery of lung-descending herbs and bioactive constituents using TRP channel-functionalized screening - Bin Yu; Jiaye Tian; Zewen Wang; Liansheng Qiao; Yanxia Liu; Qun Li; Yue Ren; Yuezhong Zhu; Li Lin; Yanling Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A New Species of Diaporthe Section Betulicola (Diaporthomycetidae, Diaporthales) From China - Yi Lan Jin; Xing Yu Luo; Kamran Habib; Yu Lin Ren; Qing Yang; Li Li Liu; Chanhom Loinheuang; Yang Chen; Qi Rui Li (New Zealand Journal of Botany, 2026)
A new species in Diaporthaceae, Diaporthe fengtaiensis sp. nov., is described and illustrated from Southwestern China. A comparative morpho‐anatomical study and multilocus phylogenetic analysis (ITS, CAL , HIS , TEF1‐α , TUB2 ) confirmed its position within the section Betulicola of the genus Diaporthe . The taxon is characterized by immersed ascomata (270–420 × 290–410 µm), relatively large asci (70–115 × 9.5–13.5 µm), and 1‐septate, fusiform ascospores (18.5–25.6 × 4.5–6.5 µm). Its positioning in a separate branch in the phylogenetic tree makes it distinct from the other known species of the section. A complete taxonomic treatment, based on two collected specimens, is provided along with molecular phylogenetic analyses.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Environmental glyphosate exposure compromises sperm quality in mice by impairing acrosome biogenesis via GOLPH3-mediated golgiphagy - Yu-Long Ren; Kai Chen; Yue Li; Yan-Zhan Jia; Hao Wang; Lin Wang (Journal of Hazardous Materials, 2026)

Porous carbon derived from molten salt thermal treatment of rice husk with ultrahigh adsorption capacity for tetracycline removal from solution: An experimental and theoretical study - Yongda Huang; Haojie Zhang; Hongyun Hu; Yang Ren; Zhong Lin; Shuaijie Yu; Jing He; Shuai Li; Sihua Xu; Hong Yao (Journal of Environmental Chemical Engineering, 2026)

Highly linear bionic strain decoupling sensor mediated by curved surface stress - Xueping Zhang; Junqiu Zhang; Jiachao Wu; Yu Chen; Xueyang Li; Wenjie Yu; Xiancun Meng; Guilin Li; Lina Ju; Bo Li; Tao Sun; Zhiwu Han; et al. (Chemical Engineering Journal, 2026)

A liquid reactive flame retardant strategy for CF/EP composites fabricated by vacuum infusion process - Mingming Yu; Jiaying Yao; Jiaxin Ma; Zhimin Gao; Dong Feng; Hao Huang; Ousheng Zhang; Wen Ye; Wang Xie; Lin Fang; Musu Ren; Jinliang Sun (Chemical Engineering Journal, 2026)

Bio-based vitrimer with superior rigidity-flexibility balance and high reprocessability fabricated via dynamic crosslinking and stepwise hot-pressing strategy - Mingming Yu; Rongbin Xiao; Xiaolei Wang; Haigang Xiao; Lin Fang; Wang Xie; Musu Ren; Jinliang Sun (Chemical Engineering Journal, 2026)

Identification of low-toxicity DNA topoisomerase I inhibitors with potential blood–brain barrier penetrability for glioblastoma therapy: structure-based virtual screening reveals promising novel Scaffolds - Ya-Lin Li; Jun Mao; Zhong Cheng; Xin-Yu Zhou; Duan-Na Zhang; Yu-Zhi Li; Zhi-Xing Cao; Ji-Xia Ren (Molecular Diversity, 2026)

A bezafibrate bearing Pt(IV) prodrug triggers ferroptosis via modulating lipid metabolism in lung cancer cells - Neng Wan; Xuan-Lin Ren; Xiang-Yu Ma; Tao Zhu; Cheng-Zhi Xie; Jing-Yuan Xu; Xin Qiao (JBIC Journal of Biological Inorganic Chemistry, 2026)

Cu2Te/Au@rGO aerogel as an efficient electrocatalyst for the bimodal electrochemical-colorimetric detection of 4-nitrotoluene - Nandini Nataraj; Agalya Mahalingam; Xinke Liu; Yu-Chien Lin; Ching-Wei Tung; Hsu-Wei Fang; Ren-Jei Chung (Process Safety and Environmental Protection, 2026)

Radioactivity of 14C, OBT, and TFWT in seafood from coastal areas of Zhejiang Province: Assessment of internal exposure to the public - Hong Ren; Kaiwen Tan; Feng Lin; Taotao Zheng; Xiaoxiang Ma; Peng Wang; Shunfei Yu; Hua Zou; Xinyu Gong; Yiyao Cao (Food Control, 2026)

Coupled CFD-DEM modeling of fine particles and fibers migration and clogging mechanisms in bridging regions - Ran Lin; Yinjian Huang; Jinzhou Zhao; Lan Ren; Zhihao Yu; Zhiqiang Li; Jianfa Wu; Yi Song; Cheng Shen (Computers and Geotechnics, 2026)

Differential contributions of microbial necromass to humification: Hyperthermophilic vs. conventional thermophilic composting - Minru Liu; Xuechang Ren; Zhenrong Lin; Kejing Fang; Kai Li; Qizhe Fan; Zhen Yu (Bioresource Technology, 2026)

Deep Shale Matrix Permeability Evolution During Well Shut-In Under True Triaxial Stress - Jinzhou Zhao; Yanshan Guo; Zhihao Yu; Lan Ren; Ran Lin; Jianfa Wu; Yi Song; Cheng Shen (Rock Mechanics and Rock Engineering, 2026)

Revealing the spatial distribution of crown base height across China based on close-range Lidar data - Zekun Yang; Zhiyong Qi; Yuling Chen; Kai Cheng; Haitao Yang; Mengxi Chen; Jiachen Xu; Yixuan Zhang; Yu Ren; Weiyan Liu; Danyang Lin; Guoran Huang; et al. (Remote Sensing of Environment, 2025)

Effects of wheat gluten amyloid fibrils as reinforcement additives on the functional properties of polyvinyl alcohol-based and pectin-based films for fruit preservation - Chia-Yu Lin; You-Ren Lai; Chia-Jung Lee; Su-Chun How; Ta-Hsien Lin; Steven S.-S. Wang (Journal of Environmental Chemical Engineering, 2025)

Optimizing the biosynthesis factors and screening the metal chelation capacity of Yersinabactin analogs from genetic engineering bacteria: The promising agents for environment protection - Haotian Liu; Huiping Ma; Ziqi Ren; Zhaoshuo Liu; Jianli Liu; Jiahe Chen; Jianxiang Ma; Yu Qiang; Zixuan Lin; Ruiquan Qi (Journal of Environmental Chemical Engineering, 2025)

Multifunctional visual photoelectrochemical sensor based on ternary Sb2WO6/P@g-C3N4/Ag2S nanocomposite for selective mercury-ion monitoring in environmental matrices and energy storage applications - Abishek Jayapaul; Sanjay Ballur Prasanna; Lu-Yin Lin; Rajalakshmi Sakthivel; Yu-Chien Lin; Ching-Wei Tung; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2025)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Long-term effects of the hydrophilic and electrophilic modified magnetic carriers on partial nitrification at low temperatures: Enhancing nitrite supply by stimulating major enzyme gene expression - Fang Man; Yi Xue; Yuexin Yu; Chengyu Gu; Sijia Ma; Yuan Lin; Hongqiang Ren; Ke Xu (Environmental Research, 2025)

Nanoengineered scheelite-structured SrWO4 decorated on MXene sheets: A novel platform for electrochemical sensing of the anti-cancer drug nilutamide with DFT insights - Akash Ashokrao Jagtap; Vaibhav Kanke; Rajalakshmi Sakthivel; Amar S. Katkar; Lu-Yin Lin; Yu-Chien Lin; Xinke Liu; Cihun-Siyong Gong; Ching-Wei Tung; Ren-Jei Chung (Environmental Research, 2025)

Validating recent global canopy height maps over China's forests based on UAV lidar data - Ang Chen; Kai Cheng; Yuling Chen; Zhiyong Qi; Haitao Yang; Yu Ren; Zekun Yang; Mengxi Chen; Jiachen Xu; Yixuan Zhang; Guoran Huang; Tianyu Xiang; et al. (Remote Sensing of Environment, 2025)

Late Holocene extreme dust events in the arid Central Asia recorded by lake sediments in Tien Shan - Min Zheng; Xiaozhong Huang; Ning Wang; Menghan Qiu; Jun Zhang; Lixiong Xiang; Shaojun Chen; Muhammad Farqan; Ruiqi Min; Tao Wang; Chong Huang; Xiuxiu Ren; et al. (Quaternary Science Reviews, 2025)

Effects of ice-binding protein from Leucosporidium sp. AY30 (LeIBP) on physicochemical quality, myofibrillar protein and ice crystal morphology of largemouth bass during air freezing - Junde Ren; Feifei Hu; Farooq Muhammad; Lihui Hu; Tao Song; Maninder Meenu; Jie Lin; Ying Liu; Hosahalli S. Ramaswamy; Yong Yu (Food Research International, 2025)

High-sensitivity Ara h1 detection with a praseodymium niobate-carbon nanofiber immunosensor - Evangeline Jafneel Nixon; Rajalakshmi Sakthivel; Yu-Chien Lin; Hsiao-Wei Wen; Ching-Wei Tung; Ren-Jei Chung (Food Chemistry, 2025)

Simultaneous carrier concentration regulation and grain boundary passivation enable over 14 % efficient Ag-alloyed kesterite solar cells - Mengyang Wang; Yu Mao; Wenjian Chan; Yuanyuan Huang; Yanmei Deng; Ziyang Ren; Ening Gu; Xianzhong Lin; Guowei Yang (Chemical Engineering Journal, 2025)

Breaking charge transport barriers with synergistic redox dynamics in cobalt tellurium oxide-modified BiVO4: Experimental and DFT insights into enhanced photoelectrochemical water oxidation - Yu-Hsuan Chiu; Hamed Cheshideh; Akash Ashokrao Jagtap; Ren-Jei Chung; Lu-Yin Lin (Chemical Engineering Journal, 2025)

Development and application of InDels and SNPs markers based on whole-genome resequencing in Chinese cabbage - Kai-Wen Liu; Wan-Jie Men; Jin-Xia Feng; Iqbal Hussain; Hui Sheng; Li-Wei Zhang; Zhong-Ren Dai; Hai-Jiang Hu; Jian-Hao Yang; Na Lei; Xiao-Lin Yu (Horticulture, Environment, and Biotechnology, 2025)

New perspective on mechanism of L-arginine in promoting skeletal muscle growth of grass carp (Ctenopharyngodon Idella): Via enhancing skeletal muscle functions and regulating energy metabolism - Qiu-Yan Chen; Yu-Long Ma; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

Self-assembled mogroside v nanomicelle system improves oral bioavailability of the magnolol - Chengzhi Liu; Lingyi Ren; Niu Liu; Mengchu Niu; Yifei Xiang; Xianhua Wu; Changhua Lin; Zhengmin Liang; Meiling Yu; Jiakang He (Food Chemistry, 2025)

Algae biofilm produces less microbe-derived dissolved organic nitrogen under higher C/N ratio conditions - Yuexin Yu; Yuan Lin; Chengyu Gu; Fang Man; Sijia Ma; Yi Xue; Hongqiang Ren; Ke Xu (Environmental Research, 2025)

Enhancing soil carbon sequestration in jasmine gardens: Differential effects of straw and biochar on mineral-associated and particulate organic carbon - Xiaoying Ren; Wenwen Yang; Liping Ye; Siyan Lin; Yuan Li; Weiqi Wang; Jordi Sardans; Junma Chen; Shiyu Chen; Siqi Yu; Li Hou; Akash Tariq; et al. (Journal of Environmental Management, 2025)

Micropatterned piezoelectric films induced by modulated corona field for weak signal detection - Fu Lv; Chenghang Yu; Bing Liu; Jiamin Lin; Zijian Hong; Yongjun Wu; Zhaohui Ren; Qilong Zhang; Shurong Dong; Jikui Luo; Juan Li; Yuhui Huang (Chemical Engineering Journal, 2025)

Correction: Three new species from the Middle Jurassic of China provide insights on wing spots diversity of Bittacidae (Insecta: Mecoptera) - Jiamiao Yu; Jinyu Wang; Yanjie Zhang; Chungkun Shih; Dong Ren; Xiaodan Lin; Hongru Yang (The Science of Nature, 2025)

Recommendations of Stable Mg, Si, V, Fe, Cu, Zn, Rb, Sr, Ag, Cd, Ba, and U Isotope Compositions for Multiple Geological References - Jinting Kang; Xuqi Chen; Xi Deng; Yuan Fang; Haichuan Jiang; Chengyihong Liu; Cuihua Luo; Xing Li; Yuchao Lin; Zhaoqi Ren; Jiaru Sheng; Xue Tang; et al. (Journal of Earth Science, 2025)

The CXCL8-CXCR2 axis promotes M2 macrophage polarization in ovarian cancer via RASGRP4-mediated mTOR-STAT3 signaling - Mi Ren; Ling-ling Chen; Lin-yin Jiang; Hui-hui Yu; Hai-zhou Ji (Apoptosis, 2025)

Microplastic-induced hypertension in rats: A two-hit model exploring oxidative stress and gut microbiota - Yu-Chun Cheng; Wei-Ling Chen; Hong-Ren Yu; Ching-Yi Tsai; Jiunn-Ming Sheen; Mao-Meng Tiao; Chien-Ning Hsu; You-Lin Tain (NanoImpact, 2025)

A new approach to color correction and equalization for generating mars global color image mosaics from Tianwen-1 MoRIC images - Xin Ren; Xiaoxia Zhang; Wangli Chen; Wei Yan; Xingguo Zeng; Xu Tan; Xingye Gao; Qiang Fu; Lin Guo; Qing Zhang; Zhaopeng Chen; Guobin Yu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Mixed-cation engineering of hybrid antimony chlorides for band gap-directing deep-blue emission - Ren-Jie He; Lin-Xia Yang; Xin-Yu Ma; Ting-Jie Wang; Zengsheng Guo; Jinling Miao; Suna Wang; Cuncheng Li; Guang-Ning Liu (Chemical Engineering Journal, 2025)

Nitrogen level determines arbuscular mycorrhizal fungi nitrogen uptake rate of Stipa purpurea in alpine steppe - Jiahui Sun; Yu Tang; Keyu Chen; Shijie Ren; Hailan Shi; Qiang Dong; Junfu Dong; Lin Zhang; Xiaoyong Cui; Yanfen Wang; Baoming Ji; Jing Zhang (Plant and Soil, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Effects of dietary Inonotus obliquus fermentation products supplementation on meat quality and antioxidant capacity of finishing pigs - Xiangyuan Li; Lin Zhang; Yimin Zhang; Xin Luo; Jiang Yu; Sufang Ren; Laixue Ni; Xianqi Yao; Jiaqiang Wu; Yanwei Mao (Meat Science, 2025)

Upcycling electroplating sludge into nanoflower-structured Cu-MOFs for efficient Fenton-like degradation of organic dyes - Jia-Yin Lin; Si-Han Yu; Jun-Ren Shih; Tsai-Hsuan Hsieh; Chih-Ying Wang; Jen-Yu Huang; Nai-Wen Tsao (Journal of Water Process Engineering, 2025)

Synergistic integration of dual Z-scheme Gd2Sn2O7/Ag3PO4/SnS2 heterojunction for accelerated visible-light photodegradation of sulfasalazine: Insights into DFT, toxicity, and antibacterial study - Akash Ashokrao Jagtap; Sanjay Ballur Prasanna; Susaritha Ramanathan; Sandeep Shadakshari; Kumara Swamy Ningappa; Yu-Chien Lin; Xinke Liu; Ching-Wei Tung; Ren-Jei Chung (Journal of Water Process Engineering, 2025)

Bifunctional approach for electrochemical detection and catalytic degradation of Rhodamine B in environmental samples using a NiFe2O4@C/PPy catalyst: Kinetic and thermodynamic insights - Mosas Vinsy Arul Thomas; Sanjay Ballur Prasanna; Akash Ashokrao Jagtap; Gagankumar Sakleshpur Kumar; Yu-Chien Lin; Rajalakshmi Sakthivel; Ching-Wei Tung; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2025)

Rational engineering of dual Z-scheme Dy₂Sn₂O₇/MoS₂/Ag@g-C₃N₄ heterostructures for efficient tetracycline photodegradation via persulphate activation: Insights from DFT and experimental characterization - Akash Ashokrao Jagtap; Dhanashri D. Khandagale; Susaritha Ramanathan; Sanjay Ballur Prasanna; Yu-Chien Lin; Norman Lu; Sea-Fue Wang; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2025)

A novel catalytic ozonation mechanism of MIL-53(Fe70Ce30): Role of abundant oxygen vacancies and unsaturated metal centers generated via Ce-doping - Hui Yu; Xiaochuan Lin; Shuxin Ren; Kaiyang Chen; Quan Sun; Min Song; Chaoqun Tan (Chemical Engineering Journal, 2025)

Three new species from the Middle Jurassic of China provide insights on wing spots diversity of Bittacidae (Insecta: Mecoptera) - Jiamiao Yu; Jinyu Wang; Yanjie Zhang; Chungkun Shih; Dong Ren; Xiaodan Lin; Hongru Yang (The Science of Nature, 2025)

Contrasting responses of flowering phenology in C 3 and C 4 plants shape grassland community structure under global change - Lu Bai; Guodong Han; Lin Jiang; Thomas W. Crowther; Constantin M. Zohner; Kailiang Yu; Zhuwen Xu; Zhongwu Wang; Qian Wu; Yi Zhu; Jinglei Tang; Haiyan Ren (Ecology, 2025)
Climate change is known to affect plant phenology. Yet, the sensitivity of flowering phenology in dryland regions to climate change, and the potential implications for community composition, remain largely unexplored. Here, we used an 18‐year field experiment to investigate the effects of climate warming and nitrogen addition on flowering phenology of four C 3 plant species and two C 4 plant species, and the cascading effects on the relative abundance of C 3 and C 4 plants in a desert steppe. Across the past 10 years of the experiment (2013–2022), we found that warming had a greater effect on phenological shifts in C 3 than in C 4 plants. Warming significantly advanced the flowering time of C 3 plants by 4.3 ± 0.1 days and of C 4 plants by 2.8 ± 0.1 days, respectively. Warming also reduced the duration of flowering by 1.8 ± 0.1 days for C 3 plants but had no effect on C 4 plants, and decreased the dominance of C 3 plants compared to C 4 plants. Nitrogen addition extended the duration of flowering of C 4 plants by 3.4 ± 0.2 days and increased their relative dominance, while decreasing the dominance of C 3 plants. Structural equation models revealed that these phenological responses were largely driven by soil temperature and soil water availability. Our results demonstrate that the different phenological responses of C 3 and C 4 plants contribute to shifts in dominance between these plant types in temperate dryland ecosystems under global changes.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Five undescribed chromone-phenylpyridone hybrids from Cineraria repanda-derived Penicillium oxalicum with cytotoxic and antibacterial activity - Yu Wei Huang; Jing Guan; Yin Tang; Ren Xiang Tan; Li Ping Lin (Phytochemistry, 2025)

Real and long-time predicting the trajectories of internal solitary waves: Case studies in the Sulu Sea - Longyu Huang; Jingsong Yang; Lin Ren; Zetai Ma; Yu Chai; Peng Chen; Shuangyan He; Bingqing Liu; Antony K. Liu (Ocean Engineering, 2025)

International research initiative on genomics-guided sugarcane breeding - Xingtan Zhang; Jungang Wang; Noor-ul-Áin; Youxiong Que; Jisen Zhang; Javeria Abid; Peifang Zhao; Yuebin Zhang; Jishan Lin; Li-yu Chen; Yixue Bao; Robert Henry; et al. (Molecular Plant, 2025)

Deciphering the role of extracellular polymeric substances in the adsorption of perfluorooctanoic acid during sludge alkaline fermentation: Experimental study and molecular dynamics simulation - Chengyu Gu; Sijia Ma; Fang Man; Yuexin Yu; Yuan Lin; Yi Xue; Yanru Wang; Hongqiang Ren; Ke Xu (Chemical Engineering Journal, 2025)

Converting static to Dynamic: Biomimetic Ultra-Sensitive Wide-Range flexible pressure sensor inspired by the Contact-Regulation process of scorpion pectines - Junqiu Zhang; Jiachao Wu; Lili Liu; Xiangbo Gu; Xueping Zhang; Xueyang Li; Zijian Shi; Yu Chen; Jiqi Gao; Junfeng Zhang; Tao Sun; Honglie Song; et al. (Chemical Engineering Journal, 2025)

Unearthing Vertical Stratified Archaeal Community and Associated Methane Metabolism in Thermokarst Sediments - Ze Ren; Mei Wang; Jinlei Yu; Lixiang Zhang; Zhenmei Lin; Xia Li; Yunlin Zhang (Environmental Microbiology, 2025)
Thermokarst lakes are hotspots for greenhouse gas emissions across the Arctic and Qinghai‐Tibet Plateau. Investigating the vertical stratification of archaeal communities in thermokarst lake sediments is essential for understanding their ecological roles and contributions to methane production. Here, we analysed archaeal communities along a depth gradient in thermokarst lake sediments. Alpha diversity (richness and Shannon index) generally decreased with depth. Euryarchaeota was the most abundant phylum, though its relative abundance declined with depth, while Thaumarchaeota increased. At the order level, Methanosarcinales and Nitrosopumilales showed increased relative abundance with depth, indicating adaptation to deeper anoxic layers, whereas Methanomicrobiales and Methanotrichales decreased. Beta diversity increased with depth, shifting from stochastic to deterministic processes. Network topology revealed reduced species connectivity but heightened modularity at depth, signalling niche specialisation. Functionally, genes associated with the initial steps of methane metabolism ( Fwd , Mtd , Mer ) increased with depth, while those involved in later steps ( Mtr , Mcr ) decreased, suggesting reduced energy conservation efficiency and lower overall methanogenesis rates in deeper sediments. These findings highlight the significant impact of vertical stratification on archaeal community structure, interaction networks, and functional capabilities.

Seasonal difference in the behavior of polycyclic aromatic hydrocarbons in a large river-dominated estuary: Significance of winter sediment resuspension - Dongrui Zhang; Xiaoxia Yu; Hongwei Ren; Xueshi Sun; Lian Duan; Tian Lin; Zhigang Guo (Marine Pollution Bulletin, 2025)

Development of a rat airway organoids model for studying chronic obstructive pulmonary disease - Chuanlai Yang; Hongwei Yang; Yangling Xian; Nanyi Liu; Haoyin Tan; Zirui Ren; Yanzhen Lin; Huan Zhao; Changjian Fang; Kang Yu; Dequan Pan; Yali Zhang; et al. (Tissue and Cell, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Conformational entropy modulation of the work function for the construction of efficient ohmic contacts to accelerate the catalytic conversion of lithium polysulfide - Jing-Zhou Chen; Yu-Jie Ren; Kuan-Kuan Tian; Bai-Qin Xiong; Dong-Lin Zhao (Chemical Engineering Journal, 2025)

Environmental Factors Influencing Groundwater Quality and Health Risks in Northern Henan Plain, China - Yu Ren; Wengeng Cao; Lihua Zhao; Shuai Wang; Deng Pan; Lin Zhang; Xiangzhi Li; Shunyu Xiao; Zeyan Li (Exposure and Health, 2025)

The impact and mechanisms of YL-IPA08, a potent ligand for the translocator protein (18 kDa) on protection against LPS-induced depression and cognitive dysfunction in rodents - Lin-yu Cui; Jing-yao Duan; Jiao-zhao Yan; Jing-ya Wang; Peng Ren; Li-ming Zhang; Wen-zhi Guo; Wei Dai; Yun-feng Li (Metabolic Brain Disease, 2025)

The effect of ice-binding protein from Leucosporidium sp. AY30 (LeIBP) on physicochemical quality and microstructure of largemouth bass during frozen storage - Junde Ren; Feifei Hu; Maninder Meenu; Lihui Hu; Yuxiao Mao; Tao Song; Jie Lin; Ying Liu; Hosahalli S. Ramaswamy; Yong Yu (Innovative Food Science & Emerging Technologies, 2025)

Photo-responsive g-C3N4/copper molybdate nanocomposites enable laser-driven multi-modal imaging, photothermal and chemodynamic therapy for hepatocellular carcinoma treatment - Kayalvizhi Samuvel Muthiah; Sathan Raj Natarajan; Selvaraj Jayaraman; Udesh Dhawan; Yu-Chien Lin; Ren-Jei Chung (Chemical Engineering Journal, 2025)

Sustainable and selective upgrade of Cu(II) to High-Value HKUST-1 from acidic electroplating wastewater - Lin Ding; Qiang Wang; Yu Luo; Yunxia Luo; Wei Ren; Hui Shi; Penghui Shao; Xubiao Luo (Chemical Engineering Journal, 2025)

Arsenic and its associated metabolism genes in Chinese soils: a comprehensive investigation of mine and paddy soils - Yu-Ting Lin; Rui-Lian Yu; Gong-Ren Hu; Jing-Wei Sun; Yu Yan (Journal of Soils and Sediments, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

International research initiative on genomics-guided sugarcane breeding - Xingtan Zhang; Jungang Wang; Noor-ul-Áin; Youxiong Que; Jisen Zhang; Javeria Abid; Peifang Zhao; Yuebin Zhang; Jishan Lin; Li-yu Chen; Yixue Bao; Robert Herry; et al. (Molecular Plant, 2025)

A nationwide survey of phthalate esters (PAEs) in tobacco leaves across China: Occurrence, spatial distribution and health risk assessment - Fei Huang; Zhaohui Ren; Baolin Liu; Yong Yu; Xiaosheng Lin (Journal of Hazardous Materials, 2025)

Accelerated photocatalytic degradation of furaltadone antibiotic over a dual Z-scheme Er2Sn2O7/NiS2/V@g-C3N4 heterostructure by persulfate under visible-light irradiation: DFT, toxicity, and antibacterial activity studies - Sanjay Ballur Prasanna; Akash Ashokrao Jagtap; Susaritha Ramanathan; Lu-Yin Lin; Yeh-Fang Duann; Gagankumar Sakaleshpur Kumar; Hema Mylnahalli Krishnegowda; Yu-Chien Lin; Ren-Jei Chung (Chemical Engineering Journal, 2025)

Ambient stable ZnBr2-assisted lead-free perovskite for enhanced piezoelectricity of polyvinylidene fluoride in versatile piezo-phototronic applications - Manikandan Venkatesan; Wei-Chun Lin; Wei-Cheng Chen; Jayashree Chandrasekar; Yu-Hang Huang; Kai-Wei Lin; Zih-Syuan Syu; Ja-Hon Lin; Wei-Hung Chiang; Wei-Ren Liu; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2025)

OsPAD1, encoding a non-specific lipid transfer protein, is required for rice pollen aperture formation - Qiming Wang; Yunlu Tian; Keyi Chen; Shanshan Zhu; Yehui Xiong; Chaolong Wang; Xiaowen Yu; Wenting Bai; Hai Zheng; Shimin You; Yang Hu; Dekun Lei; et al. (Plant Molecular Biology, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Petrogenesis of late Cretaceous high Ba–Sr granodiorites, SE Lhasa block, China: implications for the reworking of juvenile crust and continental growth - Li-Hang Lin; Ren-Zhi Zhu; Shao-Cong Lai; Jiang-Feng Qin; Yu Zhu; Shao-Wei Zhao; Min Liu (Acta Geochimica, 2025)

Modeling and analysis of explicit dynamics of foot landing - Wu Ren; Ziya Zhao; Shuaiheng He; Xueling Zhang; Kailu Zhang; Yawei Li; Fei Lin; Zhenghui Wang; Guoan Zhao; Jinlong Chang; Qianfang Jia; Yi Yu; et al. (Medical & Biological Engineering & Computing, 2025)

Quantitative predictions of protein and total flavonoids content in Tartary and common buckwheat using near-infrared spectroscopy and chemometrics - Yue Yu; Yinghui Chai; Zhoutao Li; Zhanming Li; Zhongyang Ren; Hao Dong; Lin Chen (Food Chemistry, 2025)

Synergy between single atom and nanoclusters promotes power and CO tolerant performance in PEMFCs - Jiwen Lin; Zhongyao Zhang; Jiaye Qiu; Yujie Wu; Jun Yu; Yongliang Li; Xiangzhong Ren; Lei Zhang; Zhongxin Song (Chemical Engineering Journal, 2025)

Surface chemistry regulation enables highly durable superhydrophobic coatings with environmental robustness and pH-triggered recoatability - Mei-Lin Guo; Fang Wang; Ren-Yi Sun; Chun-Bo Li; Jin-Le Li; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Urban surface-emitted longwave radiation estimation from high spatial resolution thermal infrared images using a hybrid method - Songyi Lin; Huazhong Ren; Rongyuan Liu; Jinxiang Li; Shanshan Chen; Yuanjian Teng; Wenjie Fan; Baozhen Wang; Yu Liu (Remote Sensing of Environment, 2024)

Designing a reengineered probiotic yeast to spontaneously degrade residual antibiotics in gut during antimicrobial therapy - Qian He; Zhuoyu Lin; Xiaojing Zhang; Meilin Qin; Yu Huang; Xiaoping Liao; Yahong Liu; Hao Ren; Jian Sun (Journal of Cleaner Production, 2024)

Room temperature phosphorescent carbon dot composites in aqueous solutions: synthesis, properties, and tumor diagnosis and therapy - Jiajia Ren; Lin Chen; Jinlei Du; Yongzhen Yang; Xuguang Liu; Yong Chen; Shiping Yu (Chemical Engineering Journal, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

A zircon petrochronologic perspective on raising the central Tibetan crust - Shu-Hui Ren; Yun-Chuan Zeng; Roberto Weinberg; Ji-Feng Xu; Jian-Lin Chen; Bao-Di Wang; Feng Huang; Xi-Jun Liu; Hong-Xia Yu; Ming-Jian Li (Chemical Geology, 2024)

The GaKAN2, a KANADI transcription factor, modulates stem trichomes in Gossypium arboreum - Xujiao Ren; Luying Yang; Yasir Muhammad; Yuxing Xie; Xinyi Lin; Li Yu; Yuefen Cao; Mingquan Ding; Yurong Jiang; Junkang Rong (Molecular Genetics and Genomics, 2024)

Chronic dietary exposure to glyphosate-induced connexin 43 autophagic degradation contributes to blood-testis barrier disruption in roosters - Qing Liang; Bao-You Liu; Tian-Lin Zhang; Hai-Jing Zhang; Yu-Long Ren; Hai-Peng Wang; Hao Wang; Lin Wang (Science of The Total Environment, 2024)

Unveiling the pathogenic and multidrug-resistant profiles of Vibrio alfacsensis: A potential identified threat in turbot (Scophthalmus maximus) aquaculture - Ren-Ge Hu; Lei Yang; Li-Yan Wang; Yu-Lin Yang; Hong-Jin Li; Bin-Tong Yang; Yuan-Huan Kang; Zhen-Lin Liang; Wei Cong (Journal of Hazardous Materials, 2024)

Surface S doping induced ladder-regulation of lattice oxygen on the vertical FeCoOOH for water oxidation - Ning Yu; Ren-Ni Luan; Chao-Yue Gu; Yi-Lin Dong; Guanqun Han; Han Hu; Bin Liu; Yong-Ming Chai; Bin Dong (Fuel, 2024)

Selective and stable visible-light-prompted scavenger-free photoelectrochemical strategy based on a ternary ErVO4/P@g-C3N4/SnS2 nanocomposite for the detection of lead ions in different water samples - Abishek Jayapaul; Sanjay Ballur Prasanna; Lu-Yin Lin; Yeh-Fang Duann; Yu-Chien Lin; Ren-Jei Chung (Environmental Pollution, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

TEMDI: A Temporal Enhanced Multisource Data Integration model for accurate PM2.5 concentration forecasting - Ke Ren; Kangxu Chen; Chengyao Jin; Xiang Li; Yangxin Yu; Yiming Lin (Atmospheric Pollution Research, 2024)

Storm surge induced by Tropical Storm Pabuk (2019) and its impact by track variation scenarios on the Thailand coast - Yu-Lin Tsai; Tso-Ren Wu; Eric Yen; Veerachai Tanpipat; Chuao-Yao Lin (Natural Hazards, 2024)

Biochar influences phytoremediation of heavy metals in contaminated soils: an overview and perspectives - Wei-Lin Ren; Abid Ullah; Xiao-Zhang Yu (Environmental Science and Pollution Research, 2024)

Integrated induction of silver resistance determinants and production of extracellular polymeric substances in Cupriavidus metallidurans BS1 in response to silver ions and silver nanoparticles - Jia-Xin Dai; Yanshuang Yu; Le-Xing You; Hong-Lin Zhong; Yuan-Ping Li; Ai-Jun Wang; Jon Chorover; Ren-Wei Feng; Hend A. Alwathnani; Martin Herzberg; Christopher Rensing (Chemosphere, 2024)

Visible-light-prompted photoelectrochemical sensors fabricated using Er3NbO7/P@g-C3N4/SnS2 nanocomposite for detecting mercury ion in environmental water samples - Abishek Jayapaul; Yu-Chien Lin; Ying-Chu Chen; Ting-Yu Liu; Ren-Jei Chung (Chemosphere, 2024)

Environmental explanation of prostate cancer progression based on the comprehensive analysis of polychlorinated biphenyls - Wen-Cai Zheng; Fei Lin; Qian-Ren-Shun Qiu; Yu-Peng Wu; Zhi-Bin Ke; Shao-Hao Chen; Dong-Ning Chen; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Ning Xu (Science of The Total Environment, 2024)

An unusual winter bloom of dinoflagellates with notable damage to kelp cultivation around Shandong peninsula, China - Hui-Xia Geng; Fan-Zhou Kong; Jin-Xiu Wang; Qing-Chun Zhang; Fang Li; Xin Hong; Min-Jie Song; Ziru Lian; Yu-Lin Cai; Ren-Cheng Yu (Marine Environmental Research, 2024)

Facile synthesis of tantalum decorated on iron selenide with nitrogen-doped graphene hybrid for the sensitive detection of trolox in berries: Density functional theory interpretation - Rajalakshmi Sakthivel; Chun-Chien Chou; Sanjay Ballur Prasanna; Hema Mylnahalli Krishnegowda; Sayee Kannan Ramaraj; Lu-Yin Lin; Xinke Liu; Yu-Chun Lu; Hsiao-Wei Wen; Ting-Yu Liu; Ren-Jei Chung (Food Chemistry, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Measuring Spatial Radiation Dose Distribution During Abdominal Computed Tomography Scanning with Optically Stimulated Luminescence Dosimeters - Wen-Chuan Chang; Tian-Yu Shih; Pei-Ren Fang; Cheng-Hsun Lin (Journal of Medical and Biological Engineering, 2024)
Purpose As the proportion of medical radiation exposure increases, the exposure dose has received increasing attention. When performing interventional radiological diagnosis, examiners are often exposed to radiation. Therefore, patients and medical personnel are exposed to higher amounts of radiation dose. Accordingly, we used optically stimulated luminescence dosimeters (OSLDs) to measure the ambient air kerma during abdominal CT scanning to observe the spatial distribution of the doses. Methods An abdominal CT scan under a voltage of 120 kVp was performed, and OSLDs were used for the measurement. The measurement range extended from the examination couch that serves as the center point to the walls and was divided into four areas. The OSLD measurements were undertaken at three different heights (i.e., 85, 140, and 150 cm from the floor) for spatial dose detection. The OSLDs were fixed up to lines at the three height levels. Each dosimetry point was 50 cm apart. In addition, the surface incident doses of the prosthesis's mammary gland, liver, and gonad were estimated. Results According to the spatial dose distribution at the three different heights, the maximum dose and minimum dose in front of the bore were 0.194 ± 0.008 and 0.006 ± 0.001 mGy, respectively; 2 m away from the bore, the dose reduced to 9% of the maximum dose. The surface incident doses of the mammary gland, liver, and gonad were 1.321 ± 0.121, 13.083 ± 0.642, and 13.441 ± 0.658 mGy, respectively. Conclusion The spatial dose distribution revealed that the dose was the highest at the height of 140 cm and in front of the bore. The dose on the left side was higher than that on the right side. In addition, the dose was inversely proportional to the square of the distance. If the examiners must perform interventional radiological diagnosis during CT scanning, they should put on radiation protection equipment and stand behind the bore to minimize the radiation exposure.

Verification of Seasonal Prediction by the Upgraded China Multi-Model Ensemble Prediction System (CMMEv2.0) - Jie Wu; Hong-Li Ren; Jianghua Wan; Jingpeng Liu; Jinqing Zuo; Changzheng Liu; Ying Liu; Yu Nie; Chongbo Zhao; Li Guo; Bo Lu; Lijuan Chen; et al. (Journal of Meteorological Research, 2024)

2D sheet structure of zinc molybdate decorated on MXene for highly selective and sensitive electrochemical detection of the arsenic drug Roxarsone in water samples - Nareshkumar Baskaran; Sanjay Ballur Prasanna; Kanimozhi Jeyaram; Yu-Chien Lin; Mani Govindasamy; Yang Wei; Ren-Jei Chung (Chemosphere, 2024)

Weak magnetic field promotes denitrification by stimulating ferromagnetic ion-containing metalloprotein expression - Yuan Lin; Yanting Chen; Haiyue Wang; Yuexin Yu; Yanru Wang; Sijia Ma; Laichun Wang; Hongqiang Ren; Ke Xu (Water Research, 2024)

A discrete-module-beam hydroelasticity method with finite element theory in analyzing VLFS in different engineering scenarios - Xiudi Ren; Yongqiang Chen; Yu Zhang; Xiantao Zhang; Kanmin Shen; Lin Cui; Mengyao Lu (Ocean Engineering, 2024)

Dual Z-scheme heterojunction Ce2Sn2O7/Ag3PO4/V@g-C3N4 for increased photocatalytic degradation of the food additive tartrazine, in the presence of persulfate: Kinetics, toxicity, and density functional theory studies - Sanjay Ballur Prasanna; Gagankumar Sakleshpur Kumar; Rajalakshmi Sakthivel; Karthik Chimatahalli Shanthakumar; Lu-Yin Lin; Yeh-Fang Duann; Yu-Chien Lin; Yu-Chun Lu; Ren-Jei Chung (Environmental Pollution, 2024)

Amplification-free and label-free rapid detection of Staphylococcus aureus using solution-gated graphene transistor-based DNA biosensor with hybridization enhancement by interface engineering - Jiayuan Zheng; Jinhua Li; Tianci Lin; Zhanpeng Ren; Fucheng Wang; Zhonghao Shi; Haiyang Yu; Wei Jiang; Wei Tang (Chemical Engineering Journal, 2024)

Important role of Bacillus subtilis as a probiotic and vaccine carrier in animal health maintenance - Chunmei Yuan; Xiang Ji; Yuyu Zhang; Xinli Liu; Luogang Ding; Jianda Li; Sufang Ren; Fei Liu; Zhi Chen; Lin Zhang; Wenxing Zhu; Jiang Yu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Tailoring component incorporation for homogenized perovskite solar cells - Wenhan Yang; Junmin Xia; Yuexin Lin; Hao Gu; Fengqiang Ma; Yumin Ren; Fenqi Du; Dejian Yu; Jinfeng Liao; Yiwang Chen; Guojia Fang; Shengchun Yang; et al. (Science Bulletin, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Design of a pebbles-like erbium stannate integrated with graphene nanoribbons for the anti-cancer drug nilutamide detection in water and biological samples - Abishek Jayapaul; Rajesh Kumar Panda; Sayee Kannan Ramaraj; Lu-Yin Lin; Yeh-Fang Duann; Yu-Chien Lin; Yu-Chun Lu; Wai-Ching Liu; Ching-Wei Tung; Rajalakshmi Sakthivel; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2024)

Inhibition of ER stress using tauroursodeoxycholic acid rescues obesity-evoked cardiac remodeling and contractile anomalies through regulation of ferroptosis - Feng-Juan Li; Miyesaier Abudureyimu; Zeng-Hui Zhang; Jun Tao; Asli F. Ceylan; Jie Lin; Wei Yu; Russel J. Reiter; Milad Ashrafizadeh; Jun Guo; Jun Ren (Chemico-Biological Interactions, 2024)

Nasopharyngeal carcinoma cell screening based on nuclear targeting Surface-Enhanced Raman Scattering (SERS) detection - Mengmeng Zheng; Yahui Ren; Lei Jing; Meidie Cheng; Juqiang Lin; Yun Yu (Analytica Chimica Acta, 2024)

Life cycle assessment of carbonaceous pellets used in blast furnaces in the context of “double carbon” - Chunyang Lu; Dengwei Zhang; Jie Ren; Kai Wang; Manqing Li; Chuan Wang; Guangwei Wang; Lin Xiong; Yaowei Yu (Science of The Total Environment, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

A 76-m per pixel global color image dataset and map of Mars by Tianwen-1 - Jianjun Liu; Xin Ren; Wei Yan; Wangli Chen; Xingguo Zeng; Xiaoxia Zhang; Xu Tan; Xingye Gao; Qiang Fu; Dingxin Liu; Lin Guo; Qing Zhang; et al. (Science Bulletin, 2024)

Phylogenomics and biogeographical diversification of Collabieae (Orchidaceae) and its implication in the reconstruction of the dynamic history of Asian evergreen broadleaved forests - Hong-Yu Ji; Chao Ye; Yan-Qiong Chen; Jian-Wu Li; Arief Hidayat; Jiang-Lin Miao; Jian-Hua Li; Jian-Yong Wu; Jun-Wen Zhai; Si-Ren Lan; Xiao-Hua Jin (Molecular Phylogenetics and Evolution, 2024)

A Ce2MgMoO6 double perovskite decorated on a functionalized carbon nanofiber nanocomposite for quantification of ciprofloxacin in milk and honey samples: Density functional theory interpretation - Akash Ashokrao Jagtap; Sanjay Ballur Prasanna; Gagankumar Sakaleshpur Kumar; Yu-Chien Lin; Udesh Dhawan; Yu-Chun Lu; Rajalakshmi Sakthivel; Ching-Wei Tung; Ren-Jei Chung (Chemosphere, 2024)

Seasonal predictability of SST anomalies and marine heatwaves over the Kuroshio extension region in the Copernicus C3S models - Chenguang Zhou; Hong-Li Ren; Yu Geng; Run Wang; Lin Wang (Ocean Modelling, 2024)

A new simple index for characterizing the labile heavy metal concentration in soil by diffusive gradients in thin films technique - Yang-xiao-xiao Shi; Hai-rong Xu; Jia Shen; Lin-yu Guo; Jing Yan; Jun Jiang; Zhi-neng Hong; Ren-kou Xu (Environmental Pollution, 2024)

Biomechanical properties of articular cartilage in different regions and sites of the knee joint: acquisition of osteochondral allografts - Yongsheng Ma; Qitai Lin; Xueding Wang; Yang Liu; Xiangyang Yu; Zhiyuan Ren; Yuanyu Zhang; Li Guo; Xiaogang Wu; Xiangyu Zhang; Pengcui Li; Wangping Duan; et al. (Cell and Tissue Banking, 2024)
Osteochondral allograft (OCA) transplantation involves grafting of natural hyaline cartilage and supporting subchondral bone into the cartilage defect area to restore its biomechanical and tissue structure. However, differences in biomechanical properties and donor-host matching may impair the integration of articular cartilage (AC). This study analyzed the biomechanical properties of the AC in different regions of different sites of the knee joint and provided a novel approach to OCA transplantation. Intact stifle joints from skeletally mature pigs were collected from a local abattoir less than 8 h after slaughter. OCAs were collected from different regions of the joints. The patella and the tibial plateau were divided into medial and lateral regions, while the trochlea and femoral condyle were divided into six regions. The OCAs were analyzed and compared for Young’s modulus, the compressive modulus, and cartilage thickness. Young’s modulus, cartilage thickness, and compressive modulus of OCA were significantly different in different regions of the joints. A negative correlation was observed between Young's modulus and the proportion of the subchondral bone (r = − 0.4241, P < 0.0001). Cartilage thickness was positively correlated with Young’s modulus (r = 0.4473, P < 0.0001) and the compressive modulus (r = 0.3678, P < 0.0001). During OCA transplantation, OCAs should be transplanted in the same regions, or at the closest possible regions to maintain consistency of the biomechanical properties and cartilage thickness of the donor and recipient, to ensure smooth integration with the surrounding tissue. A 7 mm depth achieved a higher Young's modulus, and may represent the ideal length.

Synergistic activation of lamellar bismuth selenide anchored functionalized carbon nanofiber for detecting hazardous carbendazim in environmental water samples - Abishek Jayapaul; Yu-Chien Lin; Lu-Yin Lin; Udesh Dhawan; Yeh-Fang Duann; Yi-Hsuan Lee; Ting-Yu Liu; Rajalakshmi Sakthivel; Ren-Jei Chung (Chemosphere, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Metabolic disturbance of short- and medium-chain chlorinated paraffins to zebrafish larva - Shuangshuang Chen; Xiaoqian Ren; Ying Yu; Lin Cheng; Guanghui Ding; Hairong Yang; Haijun Zhang; Jiping Chen; Ningbo Geng (Science of The Total Environment, 2024)

Nanozyme sensor array based on Fe, Se co-doped carbon material for the discrimination of Sulfur-containing compounds - Enxiang Ren; Haochen Qiu; Zhixuan Yu; Min Cao; Muhammad Sohail; Guo-Ping Lu; Xing Zhang; Yamei Lin (Journal of Hazardous Materials, 2024)

Potential roles of hydroxybenzoate paralytic shellfish toxins in modulating toxin biokinetics in scallops - Zhuo-Ru Lin; Hui-Xia Geng; Ren-Cheng Yu (Journal of Hazardous Materials, 2024)

Biochar as a green strategy in alleviating Cd mobility in soil and uptake in plants: A step towards Cd-free food - Abid Ullah; Wei-Lin Ren; Peng Tian; Xiao-Zhang Yu (International Biodeterioration & Biodegradation, 2024)

Melatonin alleviates glyphosate-induced testosterone synthesis inhibition via targeting mitochondrial function in roosters - Yu-Long Ren; Qing Liang; Cai-Yu Lian; Wei Zhang; Lin Wang (Environmental Pollution, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Estimation of crop residue production and its contribution to carbon neutrality in China - Xin Zhao; Ruo-Chen Li; Wen-Xuan Liu; Wen-Sheng Liu; Ying-Hao Xue; Ren-Hua Sun; Yu-Xin Wei; Zhe Chen; Rattan Lal; Yash Pal Dang; Zhi-Yu Xu; Hai-Lin Zhang (Resources, Conservation and Recycling, 2024)

Simultaneous electrochemical and colorimetric detection of tri-heavy metal ions in environmental water samples employing 3D-MOF/nickel selenide as a synergistic catalyst - Nandini Nataraj; Pranjyan Dash; Rajalakshmi Sakthivel; Yu-Chien Lin; Hsu-Wei Fang; Ren-Jei Chung (Chemical Engineering Journal, 2024)

Upgrading swin-B transformer-based model for accurately identifying ripe strawberries by coupling task-aligned one-stage object detection mechanism - Huan Liu; Xiaoxuan Wang; Feiyu Zhao; Feiyang Yu; Ping Lin; Yang Gan; Xuefeng Ren; Yongming Chen; Jian Tu (Computers and Electronics in Agriculture, 2024)

Unveiling China’s natural and planted forest spatial–temporal dynamics from 1990 to 2020 - Kai Cheng; Haitao Yang; Hongcan Guan; Yu Ren; Yuling Chen; Mengxi Chen; Zekun Yang; Danyang Lin; Weiyan Liu; Jiachen Xu; Guangcai Xu; Keping Ma; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

A top-down and in situ strategy for intrinsic acicular nanostructure enhanced ultradurable superhydrophobic and anti-icing aramid fabric - Jin-Le Li; Fang Wang; Chun-Bo Li; Ren-Yi Sun; Mei-Lin Guo; Gang Wu; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

Boron deficiency decreased the root activity of Ga-exposed rice seedlings by reducing iron accumulation and increasing Ga in iron plaque - Wei-Lin Ren; Cheng-Zhi Li; Abid Ullah; Xiao-Zhang Yu (Ecotoxicology, 2024)

Comparison of four pre-oxidants coupled powdered activated carbon adsorption for odor compounds and algae removal: Kinetics, process optimization, and formation of disinfection byproducts - Heng-Xuan Zhao; Shuang Zhang; Tian-Yang Zhang; Yi-Ping Zhu; Ren-Jie Pan; Meng-Yuan Xu; Zheng-Xiong Zheng; Chen-Yan Hu; Yu-Lin Tang; Bin Xu (Science of The Total Environment, 2024)

Direct and indirect consumption activities drive distinct urban-rural inequalities in air pollution-related mortality in China - Jingxu Wang; Jintai Lin; Yu Liu; Feng Wu; Ruijing Ni; Lulu Chen; Fangxuan Ren; Mingxi Du; Zhongyi Li; Haoyu Zhang; Zhengzhong Liu (Science Bulletin, 2024)

Numerical investigation of a semi-submersible platform interacting with steep waves using a fully nonlinear method - Zi-Lin Zhang; Shi-Li Sun; Bo-Yu Chen; Hui-Long Ren (Ocean Engineering, 2024)

CO2 enrichment and excess nitrogen supply synergistically increase toxicity of marine dinoflagellate Alexandrium minutum - Fang Li; Lin Guo; Junhui Chen; Ziru Lian; Ren-Cheng Yu (Journal of Hazardous Materials, 2024)

Enocyanin alleviates experimental colitis and restores gut microbiota homeostasis as functional foods - Cang Li; Yu Huang; Meilin Qin; Qian He; Zhuoyu Lin; Xiaojing Zhang; Hao Ren; Dan Xu; Xiaoping Liao; Yahong Liu; Jian Sun (Food Bioscience, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

2D/2D heterostructure Ni-Fe LDH/black phosphorus nanosheets with AuNP for noxious substance diphenylamine detection in food samples - Sanjay Ballur Prasanna; Yu-Chien Lin; Sayee Kannan Ramaraj; Udesh Dhawan; Xinke Liu; Ching-Wei Tung; Rajalakshmi Sakthivel; Ren-Jei Chung (Food Chemistry, 2024)

Phosphorus-containing reactive compounds to prepare fire-resistant vinyl resin for composites: Effects of flame retardant structures on properties and mechanisms - Mingming Yu; Yuji Chu; Wang Xie; Lin Fang; Ousheng Zhang; Musu Ren; Jinliang Sun (Chemical Engineering Journal, 2024)

Dual Z-scheme Pr2Sn2O7/P@g-C3N4/SnS2 heterojunctions for the removal of tetracycline antibiotic by persulfate activation: Kinetics, thermodynamic parameters, density functional theory, and toxicity studies - Sanjay Ballur Prasanna; Rajalakshmi Sakthivel; Karthik Chimatahalli Shanthakumar; Santhosh Arehalli Shivamurthy; Yu-Chien Lin; Udesh Dhawan; Xinke Liu; Ren-Jei Chung (Chemical Engineering Journal, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Association of selenium profile with neutralizing antibody response to inactivated SARS-CoV-2 vaccination - Sikang Gao; Na Ren; Taoping Sun; Qi Nie; Sitian Liu; Xuyang Geng; Yao Deng; Zefang Lin; Yu Liu; Li Zhou (Journal of Trace Elements in Medicine and Biology, 2023)

Partial denitrification-anammox granular sludge domesticated from high-strength anammox granules and the high-efficiency performance in treating low-nitrogen wastewater - Lan Lin; Zibin Luo; Yanlong Zhang; Yuanyuan Ren; Yu-You Li (Chemical Engineering Journal, 2023)

Parerythrobacter aestuarii sp. nov., Isolated from Seawater in the Tidal Region of Taizhou - Han Dong; Ren-Zhuang Han; Yu Zhang; Maripat Xamxidin; Peng Zhou; Cong Sun; Wu Qu; Lin Xu (Current Microbiology, 2023)

Overcoming the fluorescent interference during Raman spectroscopy detection of microplastics - Yu Liu; Jiale Hu; Liqian Lin; Bing Yang; Minhua Huang; Min Chang; Xiaoxin Huang; Zhenqing Dai; Shengli Sun; Lei Ren; Chengyong Li (Science of The Total Environment, 2023)

Highly responsive and sensitive non-enzymatic electrochemical sensor for the detection of β-NADH in food, environmental and biological samples using AuNP on polydopamine/titanium carbide composite - Sanjay Ballur Prasanna; Aboud Ahmed Awadh Bahajjaj; Yi-Hsuan Lee; Yu-Chien Lin; Udesh Dhawan; Rajalakshmi Sakthivel; Ren-Jei Chung (Food Chemistry, 2023)

Correction: Betaine regulates adipogenic and osteogenic differentiation of hAD-MSCs - Yue Jing; Jian Zhou; Fenghua Guo; Lin Yu; Xiaomeng Ren; Xiushan Yin (Molecular Biology Reports, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

Dynamics and performance evaluation of wind-induced vibration of a cuboid bluff body with two ornaments - He Ren; Tian-yu Zheng; Wen-yuan Lin; Hai-Tao Li; Wei-Yang Qin; Daniil Yurchenko (Ocean Engineering, 2023)

Construction and demolition waste as a high-efficiency advanced process for organic pollutant degradation in Fenton-like reaction to approach circular economy - Kuan-Ting Lee; Kuan-Yu Ho; Wei-Hsin Chen; Eilhann E. Kwon; Kun-Yi Andrew Lin; Shuenn-Ren Liou (Environmental Pollution, 2023)

Damage detection of bridges subjected to moving load based on domain-adversarial neural network considering measurement and model error - Zhi-Dong Li; Wen-Yu He; Wei-Xin Ren; Yi-Lin Li; Yi-Fan Li; Hua-Cai Cheng (Engineering Structures, 2023)

Heart valve-inspired self-lubricating anticoagulant surfaces - Yang Cheng; Zhiwei Yang; Xiaodan Gou; Qing Yang; Zichen Zhang; Shiyu Cui; Yuhua Ren; Lihong Fan; Haifeng Zhang; Zheng Fang; Yu Lu; Lin Kai; et al. (Chemical Engineering Journal, 2023)

Distribution and potential health risks of perfluoroalkyl substances (PFASs) in water, sediment, and fish in Dongjiang River Basin, Southern China - Wang Xu; Shibo Li; Weimin Wang; Ping Sun; Chunyang Yin; Xuxia Li; Liang Yu; Gang Ren; Lin Peng; Fei Wang (Environmental Science and Pollution Research, 2023)

Daphnane-type diterpenoids from Stellera chamaejasme L. and their inhibitory activity against hepatocellular carcinoma cells - Zhuo-Yang Cheng; Jing-Xian Ren; Xiao-Bian Xue; Man Wang; Xiao-Qi Yu; Bin Lin; Guo-Dong Yao; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Effects of winemaking techniques on the phenolics, organic acids, and volatile compounds of Muscat wines - Yan-lun Ju; Xue-lei Xu; Yi-ke Yu; Meng Liu; Wan-ni Wang; Jin-ren Wu; Bo-chen Liu; Yang Zhang; Yu-lin Fang (Food Bioscience, 2023)

Maternal exposure to fine particulate matter and congenital heart defects during preconception and pregnancy period: A cohort-based case-control study in the Taiwan maternal and child health database - Ya-Chu Chang; Yu-Ting Lin; Chau-Ren Jung; Ke-Wei Chen; Bing-Fang Hwang (Environmental Research, 2023)

Effects of biochar supported nano zero-valent iron with different carbon/iron ratios on two-phase anaerobic digestion of food waste - Pan Wang; Miao Yu; Peiru Lin; Yi Zheng; Lianhai Ren (Bioresource Technology, 2023)

Seed traits of reintroduced invasive populations of Triadica sebifera show few differences in comparison with those of native populations - Yu-Lin Li; Yun-Tao Xiong; Jie-Ren Jin; Chao-Nan Wang; Zhi-Li Pan; Jie Wang; Yan Wang; Yi Wang (Plant Ecology, 2023)

Comparison of nutritional quality, flesh quality, muscle cellularity, and expression of muscle growth-related genes between wild and recirculating aquaculture system (RAS)-farmed black rockfish (Sebastes schlegelii) - Xin Gao; Haojie Zhai; Zuxiang Peng; Jinxi Yu; Lin Yan; Wei Wang; Tongjun Ren; Yuzhe Han (Aquaculture International, 2023)

Positive responses and mechanisms of nitrifying sludge to carbon quantum dots: reactor performance, microbial behavior, and antioxidant defense - Lin-Kai Guo; Lei Yang; Shen Cui; Zhao Sun; Xiao-Tong Li; Yu-Chao Wang; Yu-Cai Li; Yong-Xiang Ren (Environmental Science and Pollution Research, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Origin and diversification of a Himalayan orchid genus Pleione - Sha-Sha Wu; Ming-Tao Jiang; Jiang-lin Miao; Ming-He Li; Jie-Yu Wang; Li-Ming Shen; Dong-Hui Peng; Si-Ren Lan; Jun-Wen Zhai; Zhong-Jian Liu (Molecular Phylogenetics and Evolution, 2023)

Emission and gas-particle partitioning characteristics of atmospheric halogenated and organophosphorus flame retardants in decabromodiphenyl ethane-manufacturing functional areas - Helong Ren; Xiang Ge; Zenghua Qi; Qinhao Lin; Guofeng Shen; Yingxin Yu; Taicheng An (Environmental Pollution, 2023)

A fractional-order two-surface plasticity model for over-consolidated clays and its application to deep gallery excavation - Wei Cheng; Ren-Peng Chen; Zhen-Yu Yin; Han-Lin Wang; Fan-Yan Meng (Computers and Geotechnics, 2023)

An interlayer flame retardant method to effectively fire retardant and reinforce CF/EP composites by nanofiber film intercalation - Mingming Yu; Yuji Chu; Wang Xie; Lin Fang; Xueqiang Liu; Ousheng Zhang; Musu Ren; Jinliang Sun (Chemical Engineering Journal, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

The interspecific competition of tree plants in the presence of AM fungi and litter facilitates root morphological development and nutrition when compared with intraspecific competition - Yun Guo; Kaiping Shen; Tingting Xia; Yuejun He; Wenda Ren; Pan Wu; Yan Lin; Bangli Wu; Xu Han; Lu Gao; Jinting Li; Xiaorun Hu; et al. (Environmental Science and Pollution Research, 2023)

Numerical study on unsteady propeller exciting characteristics considering shafting whirling vibration effect - Chang-Lin Meng; Zhi-Jun Shuai; Tao Yu; Ke-Xin Ren; Jie Jian; Xi Wang; Dong-Hua Wang; Wan-You Li; Chen-Xing Jiang (Ocean Engineering, 2023)

Two generations of crustal anatexis in association with two-stage exhumation of ultrahigh-pressure metamorphic rocks in the Dabie orogen - Qiong-Xia Xia; Meng Yu; Er-Lin Zhu; Ren-Xu Chen; Wan-Cai Li; Yong-Fei Zheng; Zi-Fu Zhao; Zhao-Ya Li (Lithos, 2023)

Betaine regulates adipogenic and osteogenic differentiation of hAD-MSCs - Yue Jing; Jian Zhou; Fenghua Guo; Lin Yu; Xiaomeng Ren; Xiushan Yin (Molecular Biology Reports, 2023)

Characteristics and provenances of rare earth elements and Nd isotopes in surface sediments of mangrove wetlands in the Jiulong River Estuary, China - Bo-sen Weng; Rui-an Wan; Rui-lian Yu; Gong-ren Hu; Yu Yan; Cheng-qi Lin; Hua-bin Huang (Environmental Science and Pollution Research, 2023)

Transcriptome analysis reveals the feeding response and oxidative stress in juvenile Micropterus salmoides fed a low-fish-meal diet with enzyme-hydrolysed intestinal mucosa protein substitution - Heng Yu; Xianping Ge; Lin Zhang; Xiaoru Chen; Mingchun Ren; Hualiang Liang (Aquaculture, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A volatile producing Bacillus subtilis strain from the rhizosphere of Haloxylon ammodendron promotes plant root development - Ao-Lei He; Ling-Yu Zhao; Wei Ren; Hui-Ru Li; Paul W. Paré; Qi Zhao; Jin-Lin Zhang (Plant and Soil, 2023)

Iron catalyzed organic reactions in water: A “nature-like” synthesis - Fuying Zhu; Guo-Ping Lu; Fei Wang; Enxiang Ren; Yueyi Yu; Yamei Lin (Current Opinion in Green and Sustainable Chemistry, 2023)

Photoinduced transformation of ferrihydrite in the presence of aqueous sulfite and its influence on the repartitioning of Cd - Jinwen Qiu; Xiaokang Hou; Yuan Ren; Chengshuai Liu; Fangyuan Meng; Jyh-Fu Lee; Yu-Jung Lin; Ziyuan Huang; Huanxin Ma; Zhenqing Shi; Chunhua Feng (Water Research, 2023)

Correction to: Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Superior performances via designed multiple embossments within interfaces for flexible pressure sensors - Yujing Zhang; Yuheng Wang; Chenying Wang; Yifan Zhao; Weixuan Jing; Song Wang; Yaxin Zhang; Xiangyue Xu; Fuzheng Zhang; Kaige Yu; Qi Mao; Qijing Lin; et al. (Chemical Engineering Journal, 2023)

The interaction of MC3R and MC4R with MRAP2a in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; De-Bin Zhong; Xin Ren; Hao-Lin Mo; Ze-Bin Jiang; Jia-Jia Yu; Dong-Mei Xiong; Hai-Xia Liu; Li-Xin Wang (Fish Physiology and Biochemistry, 2023)

Unique roles in health promotion of dietary flavonoids through gut microbiota regulation: Current understanding and future perspectives - Zhanming Li; Zhongyang Ren; Lin Zhao; Lin Chen; Yue Yu; Dongxu Wang; Xuejin Mao; Guangtian Cao; Zhenlei Zhao; Hongshun Yang (Food Chemistry, 2023)

Efficient activation of peroxydisulfate by a novel magnetic nanocomposite lignin hydrogel for contaminant degradation: Radical and nonradical pathways - Jiaqu Tan; Jinjin Wang; Zijun Tan; Min Yu; Zijiang Yang; Zongling Ren; Yongtao Li; Yulong Zhang; Xueming Lin (Chemical Engineering Journal, 2023)

Shanghai Autism Early Development: An Integrative Chinese ASD Cohort - Yuan Dai; Yuqi Liu; Lingli Zhang; Tai Ren; Hui Wang; Juehua Yu; Xin Liu; Zilin Chen; Lin Deng; Minyi Tao; Hangyu Tan; Chu-Chung Huang; et al. (Neuroscience Bulletin, 2022)

Transcranial Direct-Current Stimulation Regulates MCT1-PPA-PTEN-LONP1 Signaling to Confer Neuroprotection After Rat Cerebral Ischemia–Reperfusion Injury - Xiangyi Kong; Wenjie Hu; Yu Cui; Jingchen Gao; Xujin Yao; Jinyang Ren; Tao Lin; Jiangdong Sun; Yunyi Gao; Xiaohua Li; Hui Wang; Huanting Li; et al. (Molecular Neurobiology, 2022)
Propionic acid (PPA) is a critical metabolite involved in microbial fermentation, which functions to reduce fat production, inhibit inflammation, and reduce serum cholesterol levels. The role of PPA in the context of cerebral ischemia–reperfusion (I/R) injury has yet to be clarified. Increasing evidence indicate that transcranial direct-current stimulation (tDCS) is a safe approach that confers neuroprotection in cerebral ischemia injury. Here, we show that the levels of PPA were reduced in the ischemic brain following a rat cerebral I/R injury and in the cultured rat cortical neurons after oxygen–glucose deprivation (OGD), an in vitro model of ischemic injury. We found that the decreased levels of transporter protein monocarboxylate transporter-1 (MCT1) were responsible for the OGD-induced reduction of PPA. Supplementing PPA reduced ischemia-induced neuronal death after I/R. Moreover, our results revealed that the neuroprotective effect of PPA is mediated through downregulation of phosphatase PTEN and subsequent upregulation of Lon protease 1 (LONP1). We demonstrated that direct-current stimulation (DCS) increased MCT1 expression and PPA level in OGD-insulted neurons, while tDCS decreased the brain infarct volume in the MCAO rats via increasing the levels of MCT1 expression and PPA. This study supports a potential application of tDCS in ischemic stroke.

7,8-Dihydroxyflavone attenuates the virulence of Staphylococcus aureus by inhibiting alpha-hemolysin - Nan Bian; Xiangqian Chen; Xinran Ren; Zishu Yu; Mengli Jin; Xiaoyu Chen; Chang Liu; Yanhe Luan; Lin Wei; Ying Chen; Wu Song; Yicheng Zhao; et al. (World Journal of Microbiology and Biotechnology, 2022)

Effect of the interaction of fulvic acid with Pb(II) on the distribution of Pb(II) between solid and liquid phases of four minerals - Lin-yu Guo; Xian He; Zhi-neng Hong; Ren-Kou Xu (Environmental Science and Pollution Research, 2022)

Fine particulate matter measured by satellites predicts the risk of age-related macular degeneration in a longitudinal cohort study - Chung-Ling Liang; Chi-Min Wang; Chau-Ren Jung; Ya-Chu Chang; Chun-Ju Lin; Yu-Ting Lin; Bing-Fang Hwang (Environmental Science and Pollution Research, 2022)

Association between MAP3K4 gene polymorphisms and the risk of schizophrenia susceptibility in a Northeast Chinese Han population - Yang Sun; Ye Lv; Hui-Wen Ren; Guan-Yu Wang; Li-Na Xuan; Yi-Yang Luo; Zhi-Lin Luan (Metabolic Brain Disease, 2022)

Detection of bloom-forming dinoflagellates Karenia mikimotoi and Prorocentrum donghaiense using qPCR assays - Xiao-Kun Hu; Zhuo-Ru Lin; Qing-Chun Zhang; Fan-Zhou Kong; Jing-Yi Cen; Yu-Lan Zeng; Ren-Cheng Yu (Journal of Applied Phycology, 2022)

Intelligent identification method and application of seismic faults based on a balanced classification network - Jing Yang; Ren-Wei Ding; Hui-Yong Wang; Nian-Tian Lin; Li-Hong Zhao; Shuo Zhao; Yu-Jie Zhang (Applied Geophysics, 2022)

Massive Heat Shock Protein 70 Genes Expansion and Transcriptional Signatures Uncover Hard Clam Adaptations to Heat and Hypoxia - Zhi Hu; Hao Song; Jie Feng; Cong Zhou; Mei-Jie Yang; Pu Shi; Zheng-Lin Yu; Yong-Ren Li; Yong-Jun Guo; Hai-Zhou Li; Tao Zhang (Frontiers in Marine Science, 2022)
Heat shock protein 70 (HSP70) members participate in a wide range of housekeeping and stress-related activities in eukaryotic cells. In marine ecosystems, bivalves encounter abiotic stresses, including high temperatures and low dissolved oxygen. Here, 133 MmHSP70 genes were identified through combined methods including Blastp, HMM and manual filtration, based on the whole Mercenaria mercenaria genome. The MmHSP70 genes were unevenly distributed, and 41 genes (33.08%) were located on Chr 7. Phylogenetic analyses indicated that the MmHSP70 gene family mainly consisted of two clusters and the Hspa12 subfamily underwent lineage-specific expansion. A high-density collinear gene block was observed between M. mercenaria Chr 7 and Cyclina sinensis Chr 14. Tandem duplication MmHSP70 gene pairs experienced different levels of purifying selection, which could be an important source of sequence and functional constraints. MmHSP70 genes showed tissue-specific and stress-specific expression. Most tandem duplication HSP70 gene pairs had high expression under hypoxia stress. HSP70 B2 tandem duplication gene pairs showed significantly increased expression under heat plus severe hypoxia stress. This study provided a comprehensive understanding of the MmHSP70 gene family in the M. mercenaria and laid a significant foundation for further studies on the functional characteristics of MmHSP70 genes during exposure to heat and hypoxia stress.

Shear Instability and Turbulent Mixing in the Stratified Shear Flow Behind a Topographic Ridge at High Reynolds Number - Jia-Lin Chen; Xiao Yu; Ming-Huei Chang; Sen Jan; Yiing Jang Yang; Ren-Chieh Lien (Frontiers in Marine Science, 2022)
Observations on the lee of a topographic ridge show that the turbulence kinetic energy (TKE) dissipation rate due to shear instabilities is three orders of magnitude higher than the typical value in the open ocean. Laboratory-scale studies at low Reynolds number suggest that high turbulent dissipation occurs primarily within the core region of shear instabilities. However, field-scale studies indicate that high turbulence is mainly populated along the braids of shear instabilities. In this study, a high-resolution, resolving the Ozmidov-scale, non-hydrostatic model with Large Eddy Simulation (LES) turbulent closure is applied to investigate dominant mechanisms that control the spatial and temporal scales of shear instabilities and resulting mixing in stratified shear flow at high Reynolds number. The simulated density variance dissipation rate is elevated in the cusp-like bands of shear instabilities with a specific period, consistent with the acoustic backscatter taken by shipboard echo sounder. The vertical length scale of each cusp-like band is nearly half of the vertical length scale of the internal lee wave. However, it is consistent with instabilities originating from a shear layer based on linear stability theory. The model results indicate that the length scale and/or the period of shear instabilities are the key parameters to the mixing enhancement that increases with lateral Froude number Fr L , i.e. stronger shear and/or steeper ridge.

Measuring Heterogeneity in 18F-Fluorodeoxyglucose Positron Emission Tomography Images for Classifying Metastatic and Benign Bone Lesions in Patients with Cervical Cancer - Feng-Yuan Liu; Gigin Lin; Jing-Ren Tseng; Angel Chao; Huei-Jean Huang; Hung-Hsueh Chou; Yu-Chen Chang; Tzu-Chen Yen; Chyong-Huey Lai (Journal of Medical and Biological Engineering, 2021)
Purpose Heterogeneity assessment can be applied for medical imaging analysis. Here, we evaluated first-order and texture analysis (TA) metrics in 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET) imaging for classification of metastatic and benign bone lesions in patients with cervical cancer. Methods The data of 18 F-FDG PET studies performed on a specific PET/CT system from 2016 to 2018 in patients with cervical cancer were retrieved. The data of bone lesions extracted from studies over 2016–2017 and 2018 were used as training and validation datasets, respectively. Metastatic bone lesions were identified in each dataset, with an equal number of benign bone lesions selected. Cuboid volume of interest (VOI) consisting of 3 × 3 × 5 reconstructed voxels was applied for first-order metrics, and cubic VOI consisting of smaller voxels with trilinear interpolation of standardized uptake value (SUV) was adopted for TA metrics. First-order metrics included the maximum SUV (SUVmax) of lesions and the mean voxel SUV and its standard deviation (SUVsd), skewness, and kurtosis in VOI. In total, 4464 TA metrics based on 62 texture features were evaluated. Logistic regression was used for classification with area under the receiver operating characteristic curve (AUC) as the performance measure. Results From the training and validation datasets, 98 and 42 metastatic bone lesions were identified, respectively. SUVsd demonstrated higher performance than did SUVmax in both the training (AUC .798 vs .732, P = .001) and validation (AUC .786 vs .684, P < .001) datasets. Top-performing TA metrics demonstrated significantly higher performance in the training dataset, but not in the validation dataset. Conclusion A simple first-order measure of heterogeneity, SUVsd, was found to be superior to SUVmax for the classification of metastatic and benign bone lesions. Multiple hypothesis testing can result in false-positive findings in TA with multiple features and parameters; careful validation is required.

Optimizing the Wheat Seeding Rate for Wide-Space Sowing to Improve Yield and Water and Nitrogen Utilization - Zhixin Wang; Shahbaz Khan; Min Sun; Aixia Ren; Wen Lin; Pengcheng Ding; Hafeez Noor; Shaobo Yu; Yu Feng; Qiang Wang; Zhiqiang Gao (International Journal of Plant Production, 2021)

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Dicer Deletion in Astrocytes Inhibits Oligodendroglial Differentiation and Myelination - Kun Liu; Bin Yu; Jing-Fei Chen; Rui-Xue Li; Lin Chen; Shu-Yu Ren; Fei Wang; Feng Mei; Lan Xiao (Neuroscience Bulletin, 2021)
Increasing evidence has shown that astrocytes are implicated in regulating oligodendrocyte myelination, but the underlying mechanisms remain largely unknown. To understand whether microRNAs in astrocytes function in regulating oligodendroglial differentiation and myelination in the developing and adult CNS, we generated inducible astrocyte-specific Dicer conditional knockout mice (hGFAP-CreERT; Dicer fl/fl). By using a reporter mouse line (mT/mG), we confirmed that hGFAP-CreERT drives an efficient and astrocyte-specific recombination in the developing CNS, upon tamoxifen treatment from postnatal day 3 (P3) to P7. The Dicer deletion in astrocytes resulted in inhibited oligodendroglial differentiation and myelination in the developing CNS of Dicer cKO mice at P10 and P14, and did not alter the densities of neurons or axons, indicating that Dicer in astrocytes is required for oligodendrocyte myelination. Consequently, the Dicer deletion in astrocytes at P3 resulted in impaired spatial memory and motor coordination at the age of 9 weeks. To understand whether Dicer in astrocytes is also required for remyelination, we induced Dicer deletion in 3-month-old mice and then injected lysolecithin into the corpus callosum to induce demyelination. The Dicer deletion in astrocytes blocked remyelination in the corpus callosum 14 days after induced demyelination. Together, our results indicate that Dicer in astrocytes is required for oligodendroglia myelination in both the developing and adult CNS.

Game strategies in government-led eco-compensation in the Xin’an River Basin from the perspective of the politics of scale - Yisheng Ren; Lin Lu; Hu Yu; Daocai Zhu (Journal of Geographical Sciences, 2021)

Characteristics of dissolved organic matter in lakes with different eutrophic levels in southeastern Hubei Province, China - Weixiang Ren; Xiaodong Wu; Xuguang Ge; Guiying Lin; Mengdie Zhou; Zijie Long; Xinhui Yu; Wei Tian (Journal of Oceanology and Limnology, 2021)

Discovery of a naturally-occurring allele of eIF4E1.S in Nicotiana tabacum and development of a co-dominant marker - Shifeng Lin; Ralph E. Dewey; Rengang Wang; Jing Yu; Mingjin Long; Jie Zhang; Shizhou Yu; Jishun Zhang; Zili Wang; Xueliang Ren (Euphytica, 2021)

Kidney function change after transcatheter aortic valve replacement in patients with diabetes and/or hypertension - Jiaqi Fan; Changjie Yu; Kaida Ren; Wanbing Lin; Stella Ng; Zexin Chen; Xinping Lin; Lihan Wang; Qifeng Zhu; Yuxin He; Jubo Jiang; Xianbao Liu; et al. (Journal of Zhejiang University-SCIENCE B, 2021)

Structural and functional brain signatures of endurance runners - Long Cao; Yuanchao Zhang; Ruiwang Huang; Lunxiong Li; Fengguang Xia; Liye Zou; Qian Yu; Jingyuan Lin; Fabian Herold; Stephane Perrey; Patrick Mueller; Milos Dordevic; et al. (Brain Structure and Function, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Impact of Maternal Separation on Dopamine System and its Association with Parkinson's Disease - Kai-jie He; Yu-ting Zhang; Shi-zhuang Wei; Shu-min Jiang; Lin Xu; Chao Ren; Fen Wang (NeuroMolecular Medicine, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Synergistic effects of pazopanib and hyperthermia against uterine leiomyosarcoma growth mediated by downregulation of histone acetyltransferase 1 - Chiao-Yun Lin; Angel Chao; Ren-Chin Wu; Li-Yu Lee; Shir-Hwa Ueng; Chia-Lung Tsai; Yun-Shien Lee; Meng-Ting Peng; Lan-Yan Yang; Huei-Jean Huang; Hsin-Shih Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2020)

Instantaneous phase inversion based on an unwrapping algorithm - Yu-Zhao Lin; Zhen-Chun Li; Kai Zhang; Ren-Wei Ding; Ping Jiang (Applied Geophysics, 2020)

A review of progress in coupled ocean-atmosphere model developments for ENSO studies in China - Rong-Hua Zhang; Yongqiang Yu; Zhenya Song; Hong-Li Ren; Youmin Tang; Fangli Qiao; Tongwen Wu; Chuan Gao; Junya Hu; Feng Tian; Yuchao Zhu; Lin Chen; et al. (Journal of Oceanology and Limnology, 2020)

A remote sensing monitoring method for alpine grasslands desertification in the eastern Qinghai-Tibetan Plateau - Qian Kuang; Quan-zhi Yuan; Ji-chong Han; Rong Leng; Yu-shuang Wang; Ke-hong Zhu; Shuo Lin; Ping Ren (Journal of Mountain Science, 2020)

Epitranscriptomic technologies and analyses - Xiaoyu Li; Qiao-Xia Liang; Jin-Ran Lin; Jinying Peng; Jian-Hua Yang; Chengqi Yi; Yang Yu; Qiangfeng Cliff Zhang; Ke-Ren Zhou (Science China Life Sciences, 2020)

lncRNA-XIST protects the hypoxia-induced cardiomyocyte injury through regulating the miR-125b-hexokianse 2 axis - Ji-Lin Fan; Ting-Ting Zhu; Zhen-Yu Xue; Wen-Qing Ren; Jing-Qi Guo; Heng-Yi Zhao; Shi-Liang Zhang (In Vitro Cellular & Developmental Biology - Animal, 2020)

Intensity and daily pattern of passenger vehicle use by region and class in China: estimation and implications for energy use and electrification - Shiqi Ou; Rujie Yu; Zhenhong Lin; Huanhuan Ren; Xin He; Steven Przesmitzki; Jessey Bouchard (Mitigation and Adaptation Strategies for Global Change, 2020)

Instantaneous phase inversion based on an unwrapping algorithm - Yu-Zhao Lin; Zhen-Chun Li; Kai Zhang; Ren-Wei Ding; Ping Jiang (Applied Geophysics, 2020)

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Isolation of a New PAK1 Gene from Sea Cucumber (Apostichopus japonicus) and Its Expression Analysis and Function Characterization - Liyuan Ren; Kaiquan Li; Yaoyao Zhan; Yi Wang; Yao Yu; Yang Chen; Kai Lin; Jian Song; Yaqing Chang (Journal of Ocean University of China, 2019)

Real-Time Water-Level Forecasting Using Dilated Causal Convolutional Neural Networks - Jhih-Huang Wang; Gwo-Fong Lin; Ming-Jui Chang; I-Hang Huang; Yu-Ren Chen (Water Resources Management, 2019)

Effects of drought–re-watering–drought on the photosynthesis physiology and secondary metabolite production of Bupleurum chinense DC. - Linlin Yang; Yu Zhao; Qi Zhang; Lin Cheng; Mei Han; Yueying Ren; Limin Yang (Plant Cell Reports, 2019)

Complete Genome Sequence of Pseudomonas Parafulva PRS09-11288, a Biocontrol Strain Produces the Antibiotic Phenazine-1-carboxylic Acid - Yu Zhang; Ping Chen; Guoyou Ye; Haiyan Lin; Deyong Ren; Longbiao Guo; Bo Zhu; Zhongwei Wang (Current Microbiology, 2019)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Comparative transcriptomic analysis reveals adriamycin-induced apoptosis via p53 signaling pathway in retinal pigment epithelial cells - Yu-chen Lin; Ze-ren Shen; Xiao-hui Song; Xin Liu; Ke Yao (Journal of Zhejiang University-SCIENCE B, 2018)

The combination of everolimus and terameprocol exerts synergistic antiproliferative effects in endometrial cancer: molecular role of insulin-like growth factor binding protein 2 - Angel Chao; Chiao-Yun Lin; Ren-Chin Wu; Yun-Shien Lee; Li-Yu Lee; Chia-Lung Tsai; Lan-Yan Yang; Hsuan Liu; Shu-Jen Chen; Tzu-Hao Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Absorption characteristics of compound heavy metals vanadium, chromium, and cadmium in water by emergent macrophytes and its combinations - Hai Lin; Junfei Liu; Yingbo Dong; Kaiqiang Ren; Yu Zhang (Environmental Science and Pollution Research, 2018)

Hsp90 regulation affects the treatment of glucocorticoid for pancreatitis-induced lung injury - Yan Zhao; Ren-Ping Xiong; Xing Chen; Ping Li; Ya-Lei Ning; Nan Yang; Yan Peng; Yu-Lin Jiang; Yuan-Guo Zhou (Molecular and Cellular Biochemistry, 2018)

Analysis of fecal microbiota in patients with functional constipation undergoing treatment with synbiotics - Lin Sheng Huang; Cheng Kong; Ren Yuan Gao; Xuebing Yan; Hong Jing Yu; Bin Wen; Qi Zhu; Tong Yi Shen; Zhen Liang Sun; Huan Long Qin (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

In vitro and in vivo studies of nematophagous fungi Arthrobotrys musiformis and Arthrobotrys robusta against the larvae of the trichostrongylides - Kui Zheng Cai; Bo Bo Wang; Qiang Xu; Jun Lin Liu; Kang Ying Wang; Yu Jia Xue; Hai Yan Zhang; Hai Yu Wang; Xin Cao; Zhong Ren Ma (Acta Parasitologica, 2017)
Six isolates of

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

Controlling effects of surface crusts on water infiltration in an arid desert area of Northwest China - Jin-Ling Yang; Gan-Lin Zhang; Fei Yang; Ren-Min Yang; Chen Yi; De-Cheng Li; Yu-Guo Zhao; Feng Liu (Journal of Soils and Sediments, 2016)

Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2016)

FGF21 ameliorates nonalcoholic fatty liver disease by inducing autophagy - Shenglong Zhu; Yunzhou Wu; Xianlong Ye; Lei Ma; Jianying Qi; Dan Yu; Yuquan Wei; Guangxiao Lin; Guiping Ren; Deshan Li (Molecular and Cellular Biochemistry, 2016)

CLEC5A is critical for dengue virus-induced osteoclast activation and bone homeostasis - Ya-Lang Huang; Szu-Ting Chen; Ren-Shyan Liu; Yen-Hsu Chen; Chun-Yu Lin; Chung-Hao Huang; Pei-Yun Shu; Ching-Len Liao; Shie-Liang Hsieh (Journal of Molecular Medicine, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Development of Home-Based Frailty Detection Device Using Wireless Sensor Networks - Chung-Chih Lin; Chun-Chang Chen; Pay-Shin Lin; Ren-Guey Lee; Jing-Siang Huang; Tsai-Hsuan Tsai; Yu-Chuan Chang (Journal of Medical and Biological Engineering, 2016)

Regeneration of cerium(IV) in different spent chromium-etching solutions collected from thin-film transistor liquid crystal display manufacturing factories - Kuo-Lin Huang; Te-San Chen; Ren-Wei Tsai; Yu-Syuan Chen (Clean Technologies and Environmental Policy, 2016)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Nucleotide composition bias and codon usage trends of gene populations in Mycoplasma capricolum subsp. capricolum and M. agalactiae - XIAO-XIA MA; YU-PING FENG; JIA-LING BAI; DE-RONG ZHANG; XIN-SHI LIN; ZHONG-REN MA (Journal of Genetics, 2015)

Association Between a Variant in ADAMTS5 and the Susceptibility to Hepatocellular Carcinoma in a Chinese Han Population - Chongyi Li; Yanli Xiong; Zhaoyang Zhong; Shiheng Zhang; Yu Peng; Lin’ang Wang; Nan Dai; Mengxia Li; Tao Ren; Lixia Gan; Dong Wang (Cell Biochemistry and Biophysics, 2015)

Rapid emergence of a PB2-E627K substitution confers a virulent phenotype to an H9N2 avian influenza virus during adaption in mice - Xiaoyu Sang; Airong Wang; Tongjie Chai; Xijun He; Jie Ding; Xiaolong Gao; Yuanguo Li; Kun Zhang; Zhiguang Ren; Lin Li; Zhijun Yu; Tiecheng Wang; et al. (Archives of Virology, 2015)

Assessing the authenticity of commercial deep-sea drinking water by chemical and isotopic approaches - Tsung-Ren Peng; Wen-Jui Liang; Tsang-Sen Liu; Yu-Wen Lin; Wen-Jun Zhan (Isotopes in Environmental and Health Studies, 2015)

Contamination of commercially available seafood by key diarrhetic shellfish poisons along the coast of China - Chao Lin; Zeng-Shan Liu; Cai-Yun Tan; Yi-Ping Guo; Lin Li; Hong-Lin Ren; Yan-Song Li; Pan Hu; Sheng Gong; Yu Zhou; Shi-Ying Lu (Environmental Science and Pollution Research, 2015)

Suppression of PI3K/Akt signaling by synthetic bichalcone analog TSWU-CD4 induces ER stress- and Bax/Bak-mediated apoptosis of cancer cells - Meng-Liang Lin; Shih-Shun Chen; Ren-Yu Huang; Yao-Cheng Lu; Yu-Ren Liao; Mopuru Vijaya Bhaskar Reddy; Chuan-Chun Lee; Tian-Shung Wu (Apoptosis, 2014)

Molecular characterization of a new member of the 16SrV group of phytoplasma associated with Bischofia polycarpa (Levl.) Airy Shaw witches’ -broom disease in China by a multiple gene-based analysis - F. Lai; C. S. Song; Z. G. Ren; C. L. Lin; Q. C. Xu; Y. Li; C. G. Piao; S. S. Yu; M. W. Guo; G. Z. Tian (Australasian Plant Pathology, 2014)

Spatial and temporal analysis of drought risk during the crop-growing season over northeast China - Xingyang Yu; Xingyuan He; Haifeng Zheng; Ruichao Guo; Zhibin Ren; Dan Zhang; Jixiang Lin (Natural Hazards, 2014)

Identification of Key Licorice Constituents Which Interact with Cytochrome P450: Evaluation by LC/MS/MS Cocktail Assay and Metabolic Profiling - Xue Qiao; Shuai Ji; Si-wang Yu; Xiong-hao Lin; Hong-wei Jin; Yao-kai Duan; Liang-ren Zhang; De-an Guo; Min Ye (The AAPS Journal, 2014)

The role of MrbHLH1 and MrMYB1 in regulating anthocyanin biosynthetic genes in tobacco and Chinese bayberry (Myrica rubra) during anthocyanin biosynthesis - Xiao-Fen Liu; Xue-Ren Yin; Andrew C. Allan; Kui Lin-Wang; Yan-Na Shi; Yu-Ji Huang; Ian B. Ferguson; Chang-Jie Xu; Kun-Song Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Anti-neuroinflammatory Effect of a Novel Caffeamide Derivative, KS370G, in Microglial cells - Dah-Yuu Lu; Bor-Ren Huang; Wei-Lan Yeh; Hsiao-Yun Lin; Shiang-Suo Huang; Yu-Shu Liu; Yueh-Hsiung Kuo (Molecular Neurobiology, 2013)

The effects of the codon usage and translation speed on protein folding of 3Dpol of foot-and-mouth disease virus - Xiao-xia Ma; Yu-ping Feng; Jun-lin Liu; Bing Ma; Li Chen; Yong-qing Zhao; Peng-hui Guo; Jun-zhen Guo; Zhong-ren Ma; Jie Zhang (Veterinary Research Communications, 2013)

Application of a web-based remote agro-ecological monitoring system for observing spatial distribution and dynamics of Bactrocera dorsalis in fruit orchards - Joe-Air Jiang; Tzu-Shiang Lin; En-Cheng Yang; Chwan-Lu Tseng; Chia-Pang Chen; Chung-Wei Yen; Xiang-Yao Zheng; Chun-Yi Liu; Ren-Hau Liu; Yu-Fan Chen; Wan-Yi Chang; Cheng-Long Chuang (Precision Agriculture, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Production of monoclonal antibody and application in indirect competitive ELISA for detecting okadaic acid and dinophytoxin-1 in seafood - Shi-Ying Lu; Yu Zhou; Yan-Song Li; Chao Lin; Xian-Mei Meng; Dong-Ming Yan; Zhao-Hui Li; Shi-Yu Yu; Zeng-Shan Liu; Hong-Lin Ren (Environmental Science and Pollution Research, 2012)

Development of a fluorescent-intercalating-dye-based reverse transcription loop-mediated isothermal amplification assay for rapid detection of seasonal Japanese B encephalitis outbreaks in pigs - C. J. Tian; Z. X. Lin; X. M. He; Q. Luo; C. B. Luo; H. Q. Yu; R. Chen; X. W. Wu; D. Z. Zhu; Z. J. Ren; Y. Z. Bi; J. Ji (Archives of Virology, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

The combined influence of background climate and urbanization on the regional warming in Southeast China - Peng Si; Yu Ren; Dongpo Liang; Bingwen Lin (Journal of Geographical Sciences, 2012)

Distribution and expression characteristics of triterpenoids and OSC genes in white birch (Betula platyphylla suk.) - Jing Yin; Chun-Lin Ren; Ya-Guang Zhan; Chun-Xiao Li; Jia-Lei Xiao; Wei Qiu; Xin-Yu Li; Hong-Mei Peng (Molecular Biology Reports, 2012)

The impact of iron oxide magnetic nanoparticles on the soil bacterial community - Shiying He; Youzhi Feng; Hongxuan Ren; Yu Zhang; Ning Gu; Xiangui Lin (Journal of Soils and Sediments, 2011)

Detection of porcine circovirus type 1 in commercial porcine vaccines by loop-mediated isothermal amplification - Chun Wang; Victor Fei Pang; Chian-Ren Jeng; Fan Lee; Yu-Wen Huang; Yeou-Liang Lin; Shih-Hsuan Hsiao; Shiow-Suey Lai (Folia Microbiologica, 2011)

Biosynthesis of 2-amino-2,3-dimethylbutyramide by nitrile hydratase from a newly isolated cyanide-resistant strain of Rhodococcus qingshengii - Zhi-Jian Lin; Ren-Chao Zheng; Yu-Guo Zheng; Yin-Chu Shen (Biotechnology Letters, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Abnormal pain response in pain-sensitive opiate addicts after prolonged abstinence predicts increased drug craving - Zhen-Yu Ren; Jie Shi; David H. Epstein; Jun Wang; Lin Lu (Psychopharmacology, 2009)

Effect of calmidazolium on [Ca2+]i and viability in human hepatoma cells - Wei-Chuan Liao; Chorng-Chih Huang; He-Hsiung Cheng; Jue-Long Wang; Ko-Long Lin; Jin-Shiung Cheng; Kuo-Liang Chai; Pei-Te Hsu; Jeng-Yu Tsai; Yi-Chien Fang; Yih-Chau Lu; Hong-Tai Chang; et al. (Archives of Toxicology, 2009)

Induction of G2/M phase arrest and apoptosis by a novel enediyne derivative, THDA, in chronic myeloid leukemia (K562) cells - Zchong-Zcho Wu; Ching-Ming Chien; Sheng-Huei Yang; Yi-Hsiung Lin; Xiu-Wei Hu; Yu-Jhang Lu; Ming-Jung Wu; Shinne-Ren Lin (Molecular and Cellular Biochemistry, 2006)

Structure and function of glucose-6-phosphate dehydrogenase-deficient variants in Chinese population - Weiying Jiang; Guolong Yu; Peng Liu; Qian Geng; Luming Chen; Qundi Lin; Xiaoqin Ren; Wenhong Ye; Yongshu He; Yibin Guo; Shan Duan; Jing Wen; et al. (Human Genetics, 2006)

Distribution of lead in urban soil and its potential risk in Shenyang City, China - Jin-da Wang; Hui-min Ren; Jing-shuang Liu; Jun-bao Yu; Xue-lin Zhang (Chinese Geographical Science, 2006)

Pilot-Scale Fermentation and Purification of the Recombinant Allophycocyanin Over-Expressed in Escherichia coli - Baosheng Ge; Zhihong Tang; Liping Lin; Yuhong Ren; Yu Yang; Song Qin (Biotechnology Letters, 2005)

Allelic and locus heterogeneity in autosomal recessive gelatinous drop-like corneal dystrophy - Zhaoxia Ren; Pei-Yu Lin; Gordon K. Klintworth; Fumino Iwata; Francis L. Munier; Daniel F. Schorderet; Leila El Matri; Veena Theendakara; Surendra Basti; Madhukar Reddy; Fielding J. Hejtmancik (Human Genetics, 2002)